Cryptic Interactions in a Marine Microcosm: Sponges Shape the Microbiome of a Resident Goby - Ingrid Vasconcellos Bunholi; Abbie Affleck; Kallen Johnson; Reynaldo Ortega; Christopher J. Freeman; Theresa Rueger; Jordan M. Casey (Molecular Ecology, 2026)
Microbial symbionts influence ecological and evolutionary processes in their multicellular hosts; yet they remain poorly characterised in marine systems. Sponges host exceptionally diverse microbiomes, potentially providing rich microbial reservoirs for their residents. The tusked goby ( Risor ruber ), an obligate sponge‐dweller, and its sponge hosts provide an ideal model to investigate the causes and consequences of shared microbial taxa in host–resident systems. Using 16S rRNA sequencing, we characterised the microbiomes of R. ruber skin and gut, their sponge hosts, a non‐obligate, sponge‐associated goby ( Elacatinus prochilos ) and seawater. We quantified microbial overlap among hosts, examined ontogenetic patterns of shared microbiomes across goby body size and assessed the putative ecological benefits of shared microbial taxa for R. ruber . We reveal more than 500 microbial ASVs shared between R. ruber and their sponge hosts. The unique microbial overlap between R. ruber and their sponge hosts far exceeded overlap with E. prochilos and seawater. Shared taxa are putatively linked to nutrient acquisition, vitamin biosynthesis and pathogen defence, suggesting potential benefits for R. ruber from inhabiting microbially rich sponges . The proportion of the shared microbiome between R. ruber gut and sponges declines with goby body size, which suggests that the goby may undergo ontogenetic changes in diet or gut development . Thus, sponges provide more than shelter: they may function as microbial reservoirs and nutritional sources for residents. These findings underscore the need to protect microbially rich habitats and further study host–resident microbial interactions in marine systems and beyond.

Association of area deprivation index and median household income with early postoperative outcomes after spine tumor surgery - Kristen H. Park; Joshua L. Golubovsky; Jennifer Cirvello; Emily Xu; Scott D. McClintock; Anish Butala; Gabrielle W. Peters; Alvand Hassankhani; Hayley M. Knollman; James Schuster; Colbey W. Freeman; Neil R. Malhotra (Next Research, 2026)

Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Small peptides guard the gate of plant immunity - Nicole A. Freeman; Ujjal J. Phukan; Yiqing Wang; Sydney A. Greer; M. Shahid Mukhtar (Trends in Plant Science, 2026)

Where and how can WASH work? Understanding limited impacts from a randomized control trial of water, sanitation, and hygiene interventions in a high burden setting - Alicia N.M. Kraay; Andrew F. Brouwer; Mondal H. Zahid; Sammy Njenga; John M. Colford; Matthew C. Freeman; Joseph N.S. Eisenberg (International Journal of Hygiene and Environmental Health, 2026)

Species‐specific processing of fluorescent dissolved organic matter by Caribbean sponges - Jacqueline G. Keleher; Cole G. Easson; Christopher J. Freeman; Robert W. Thacker; Craig E. Nelson; Alicia M. Reigel; Cara L. Fiore (Limnology and Oceanography, 2026)
Coral reefs are biodiverse and productive ecosystems that are found in typically oligotrophic environments. Many studies have attempted to explain this paradox by demonstrating that microbial symbionts expand metabolic capabilities of host animals. However, few studies have determined if and how coexisting organisms and their symbiotic microbial communities partition available dissolved organic matter. To address this question, we built an artificial reef near the Florida Keys using dominant emergent sponges found in the Caribbean. Fluorescent dissolved organic matter (fDOM) components were measured in incurrent and excurrent water samples of 5–7 biological replicates for each of 10 sponge species. Sponges generally consumed more fDOM as incurrent concentrations increased, but there were also species‐level differences in their responses. We found that microbial abundance (i.e., high and low microbial abundance HMA/LMA classification) explained less variation in fDOM processing than sponge species. Additionally, fDOM analysis revealed both a separation of sponges into two groups based on whether they were net producers or consumers of fDOM, as well as their responses to fDOM concentrations in ambient seawater across species. Differential consumption of fDOM components also yielded species‐specific fluxes of fDOM. This observation contrasts with broad uptake of all fDOM components, which would be expected if net consumption of fDOM was simply concentration dependent and the same for all species. These results provide the first support for species‐level resource partitioning of fluorescent dissolved organic matter across coexisting sponge species and provide additional support for the evolutionary importance of microbial communities in sponges.

Uncertainty Quantification of Geologic Energy Storage in Depleted Gas Reservoirs Using Material Balance Equations Embedded in a Hierarchical Errors-in-Variables Model - Ashton M. Wiens; Matthew M. Jones; Philip A. Freeman; Marc L. Buursink (Mathematical Geosciences, 2026)
The storage potential for gas in geologic settings, such as depleted hydrocarbon reservoirs and solution-mined salt caverns, is becoming salient to future energy infrastructure planning. Technologies such as carbon capture, utilization, and storage, carbon dioxide-enhanced oil recovery, and natural gas and hydrogen storage help meet growing energy demands, reduce carbon emissions to meet climate goals, and provide energy security amid geopolitical uncertainties. Therefore, estimates of underground gas storage capacity could be useful for efficiently navigating the energy transitions. Material balance is a fundamental method in reservoir engineering for estimating original gas in place and potential storage capacity at the scale necessary for national assessments of subsurface pore space resources. However, the deterministic method cannot accommodate multiple data sources or quantify uncertainty in predictions. In this study, a method that embeds material balance equations within a hierarchical errors-in-variables model is proposed which allows the estimation of the distributions of reservoir properties needed for assessments. Uncertainties associated with these reservoir properties have traditionally been expert-elicited, whereas the uncertainty estimates from the proposed models are data-driven. Capacity and uncertainty estimates can be used in a probabilistic resource assessment, supplementing information traditionally used by assessors or even replacing this expert elicitation step when data are unavailable. Various regression models are compared in a case study of the Michigan Basin, a large contributor to the United States’ current natural gas storage capacity. In particular, errors-in-variables models help ameliorate regression dilution and can quantify uncertainty in predictions of pressure in addition to storage capacity. Overfitting is addressed by quantifying generalization error and model averaging in simple and stratified cross-validation against reported working gas capacity, representing the varying quality and quantity of available data. Incorporating a statistical framework into existing numerical methods in reservoir engineering can improve the quality of estimation, and in particular, this method brings rigor to uncertainty quantification as part of a larger effort by the U.S. Geological Survey to assess domestic energy gas storage resources in depleted hydrocarbon reservoirs.

Pancreatic islet remodeling in horses with hyperinsulinemia and pituitary dysfunction - P. Teague; M. Dark; D. Verdugo; D. Freeman; D. McFarlane (Domestic Animal Endocrinology, 2026)

Examining the effect of neighborhood sanitation coverage on childhood diarrheal disease in rural Bangladesh - Hannah Van Wyk; Andrew F. Brouwer; Jesse Contreras; Mahbubur Rahman; Mahfuza Islam; Amy J. Pickering; Benjamin F. Arnold; Stephen P. Luby; John M. Colford; Matthew Freeman; Ayse Ercumen; Joseph N.S. Eisenberg (International Journal of Hygiene and Environmental Health, 2026)

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Restoration of ecological interactions: The influence of site and landscape factors - B.A. Woodcock; E. Waddell; M.G. Weites; M. Guy; M. Freeman; K. Park; E. Fuentes-Montemayor; K. Watts; R.J. Barnett; S. l. Rogerson; A. Opris; J. Harris; et al. (Agriculture, Ecosystems & Environment, 2026)

Phytoplankton Biomass Dynamics in Wet (2019) and Dry (2023) Years in Lake Pontchartrain Estuary, Louisiana from Sentinel 2-MSI and PACE-OCI Observations - Shiwani Shrestha; Bingqing Liu; Jiang Li; Wei Huang; Melissa M. Baustian; Eurico J. D'Sa; Sibel Bargu; Francesca Messina; Ioannis Y. Georgiou; Abhishek Kumar; Angelina Freeman; Scott Mize (Science of The Total Environment, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Preclinical safety evaluation of sodium l-methylfolate - Keith Morris-Schaffer; Sarah Dahlberg; Esther Johann; Mary M. Murphy; Nga L. Tran; Elaine L. Freeman (Food and Chemical Toxicology, 2026)

The amphibians of Betampona: an updated account of the remarkable diversity of Madagascar’s central-eastern Strict Nature Reserve - Costanza Piccoli; Alessio Paoletti; Franco Andreone; Karen Freeman; Georges; D. James Harris; Honoré Lava; Martim Melo; Jean Nöel; Dina L. Ramamonjisoa; Randriamialisoa; Achille P. Raselimanana; et al. (Systematics and Biodiversity, 2025)

Necroptosis induced by MLKL overexpression in liver triggers cellular senescence and leads to chronic inflammation and fibrosis - Ramasamy Selvarani; Sunho Lee; Mani Saminathan; Puvarajan Boovalingam; Kavitha Kurup; Kevin Pham; Roman F. Wolf; Willard M. Freeman; Archana Unnikrishnan; Arlan Richardson (GeroScience, 2025)
Cellular senescence and necroptosis are two cell fates, which trigger an inflammatory response and increase with age, that have been proposed to play a role in inflammaging. In this study, we performed the first study to directly test the possible interaction between necroptosis and cellular senescence. Using a novel Mlkl -KI mouse model, we were able to specifically induce (~ 4-fold) the overexpression of MLKL, the necroptotic executioner, in hepatocytes (h Mlkl -KI mice). The overexpression of MLKL led to increased necroptosis and cell damage/death in liver, as shown by increased levels of MLKL-oligomers, TUNEL staining, and Ki-67 staining in the livers, as well as increased ALT activity and HMGB1 levels in the plasma. The increase in necroptosis was paralleled by an increase in cellular senescence. We observed increased levels of p16 INK4A and p21 Clip1/Waf1 as well as SASP-factors. As expected, inflammation, as measured by the levels of proinflammatory factors and mononuclear cell clusters, was increased in the h Mlkl -KI mice. Transcriptomic analysis revealed that MLKL overexpression altered the expression of genes involved in cellular senescence, inflammation, and drug metabolism. The increase in inflammation, necroptosis, and cellular senescence in the livers of 6-month-old h Mlkl -KI mice was associated with an increase in liver fibrosis. The data from our study suggest that necroptosis has the potential of inducing inflammation through two pathways: (1) the initial inflammatory storm triggered by DAMPs released from necroptotic, dying cells and (2) SASP-factors produced by senescent cells that were induced by necroptosis. Graphical abstract

Effects of residual PAH exposure from firefighters’ skin and turnout gear on biospecimen microRNA expression - Jooyeon Hwang; Jenny R. Gipson; Chao Xu; Timothy VanWagoner; Xin Xu; Robert J. Agnew; Willard M. Freeman (Environmental Research, 2025)

Effects of TPA023B, an α2/3/5GABAA subtype-selective partial allosteric modulator, on fentanyl-induced respiratory depression in male rats: comparison with the non-selective benzodiazepine midazolam - Loc M. Pham; Andria B. Nanney; Jordan Hasting; Daniela Rüedi-Bettschen; Kevin B. Freeman; James K. Rowlett (Psychopharmacology, 2025)
Rationale Opioid-related overdose deaths involving benzodiazepines have increased in recent years, and prior studies have reported that clinically used benzodiazepines can enhance the respiratory-depressant effects of mu opioid receptor (MOR) agonists. TPA023B is an α1-sparing GABA A positive allosteric modulator developed as a potential anxiolytic with fewer benzodiazepine-typical side effects. However, it is unknown if and to what degree TPA023B can affect MOR-agonist induced respiratory depression. Objectives The current study compared the effects of either TPA023B or midazolam, alone and combined with fentanyl, on respiratory depression in rats, using whole-body plethysmography. Methods Male Sprague-Dawley rats were implanted with chronic indwelling intravenous (i.v.) catheters for drug infusions. Respiration (frequency, tidal volume, and minute volume) was measured using whole-body plethysmography. The tests consisted of a pretreatment (midazolam, 30 mg/kg; i.v.; TPA023B, 1.0 mg/kg; i.v; or vehicle) followed by a fentanyl injection (0.01, 0.03, 0.1 mg/kg, i.v., or vehicle) and 60 min of respiration assessment. Results Overall, fentanyl alone, but not TPA023B or midazolam alone, produced dose-dependent reductions in tidal volume and minute volume. When administered as pre-treatments, neither midazolam nor TPA023B increased the magnitude of fentanyl-induced respiratory depression, instead producing prolonged reductions in tidal volume and minute volume. Midazolam produced a more sustained reduction in these parameters than TPA023B. Conclusions Benzodiazepines prolong fentanyl-induced respiratory depression, but this effect may be reduced by eliminating activity at α1GABA A receptor subtypes.

Florida red tides and adverse birth outcomes: Investigating harmful algae as a novel environmental exposure - Rain E. Freeman; Quynh Anh Nguyen; Sandy Haaf; Jason L. Salemi; Catherine M. Bulka (Chemosphere, 2025)

P28-35 Xylene: weight of evidence approach case study to determine the need for an extended one generation reproductive study with a developmental neurotoxicity animal cohort - L. Higgins; C. Haines; F. Faulhammer; M. Rooseboom; N. Aygun Kocabas; J.H. Arts; A. Cordova; E. Freeman; M. Nahar; E. Richmond; S. Schneider; K. Morris-Schaffer (Toxicology Letters, 2025)

Permeate fluxes from desalination of brines and produced waters: A reactive transport modeling study - Sergi Molins; Nicolas Spycher; Sarah M. Dischinger; Mostafa Nassr; Ji Yeon Lee; Jacob Johnston; Nils Tilton; Kristofer L. Gleason; Benny D. Freeman; William T. Stringfellow; Daniel J. Miller (Applied Geochemistry, 2025)

Pacific Northwest birds have shifted their abundances upslope in response to 30 years of warming temperatures - Benjamin G. Freeman; Harold N. Eyster; Julian M. Heavyside; Daniel A. Yip; Monica H. Mather; F. Louise Waterhouse (Ecology, 2025)
Mountain species are predicted to respond to warming temperatures by moving to higher elevations that remain relatively cool. Species can track warming by shifting their entire distributions upwards (the “escalator to extinction” hypothesis) or by increasing in abundance in the upper portion of their elevational range while maintaining stable elevational limits (the “upslope lean” hypothesis). Alternatively, mountain species may not change their abundance or distribution despite climate change (the “persist‐in‐place” hypothesis). Here we evaluate these three contrasting hypotheses by analyzing responses of breeding forest bird species to three decades of warming in southwestern British Columbia, Canada. Consistent with the upslope lean hypothesis, species' optimum elevations (elevations of highest abundance) increased by an average of 126 m, approximately tracking upslope movements in temperature isotherms. In contrast, species' elevational range limits were stable on average, contra the escalator to extinction hypothesis. Many individual species had stable distributions and abundances, and species with upslope abundance increases typically maintained stable abundances within the lower elevation portions of their range. Taken together, most species in our study region appear to be responding neutrally or favorably to warming temperatures. Nevertheless, one mountain species, the Canada Jay, Canada's national bird, is declining and vulnerable to the escalator to extinction within our study region. Overall, we emphasize the importance of empirical data—and abundance data in particular—when evaluating mountain species' vulnerability to climate change.

A decade of implementing the Biodiversity management plan for African penguins – successes, failures and lessons learnt - Lorien Pichegru; Millicent Makoala; Barbara J. Barham; Peter J. Barham; Desiré Dalton; Katta Ludynia; Mandy Freeman; Deon Geldenhuys; Christina Hagen; Gabby Harris; Alison Kock; Cloverley Lawrence; et al. (Journal for Nature Conservation, 2025)

Traditional and industrial approaches to oil palm cultivation alter the biodiversity of ground-dwelling arthropods in Liberia (West Africa) - Jonathan H. Timperley; Brogan L. Pett; Bility Geninyan; Ari Saputra; Abraham Vincent; Romeo Weah; Benedictus Freeman; Marshall Guahn; Peter M. Hadfield; Morris T. Jah; Tiecanna Jones; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2025)

Methylation array signals are predictive of chronological age without bisulfite conversion - Hunter L. Porter; Victor A. Ansere; Ram Babu Undi; Walker Hoolehan; Cory B. Giles; Chase A. Brown; David Stanford; Mark M. Huycke; Willard M. Freeman; Jonathan D. Wren (GeroScience, 2025)
DNA methylation data has been used to make “epigenetic clocks” which attempt to measure chronological and biological aging. These models rely on data derived from bisulfite-based measurements, which exploit a semi-selective deamination and a genomic reference to determine methylation states. We found that non-methylation factors lead to “pseudomethylation” signals that are both confounding of epigenetic clocks and uniquely age predictive. We also failed to predict age using human genotyping arrays, but found that epigenetic clocks were overrepresented near genomic regions whose methylation state is dependent upon sequence variants. Quantifying these covariates in aging studies will be critical to building better clocks and designing appropriate studies of epigenetic aging.

Investigating zinc’s role in mitigating blood lead levels’ toxicity on gut microbiota diversity: NHANES 2007–2010 - Kathyrn R. Ayres; Juan P. Liuzzi; Freeman C. Lewis; Huda M. Mobarki (Toxicology Letters, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Metabolic gene expression differences in emaciated and moderately conditioned horses: RNA-seq analysis of postmortem skeletal muscle - M. Parr; E. Shepherd; M. Hines; L. Strickland; T. Freeman; S. Moisa; J. Beever; J. Ivey (Journal of Equine Veterinary Science, 2025)

Occupational pesticide use and relative leukocyte telomere length in the biomarkers of exposure and effect in agriculture study - Patricia A. Erickson; Vicky C. Chang; Shisi He; Casey Dagnall; Kedest Teshome; Mitchell J. Machiela; Kathryn Hughes Barry; Edna F.R. Pereira; Shahinaz M. Gadalla; Christine G. Parks; Sonja I. Berndt; Laura E. Beane Freeman; et al. (Environmental Research, 2025)

Homing navigation is optimized to diurnal constraints in a tropical seabird, the red-footed booby - Joshua Coste; Stephen C. Votier; Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Peter Carr; Hannah Wood; Alice M. Trevail (Animal Behaviour, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Impact of water, sanitation, and hygiene indicators on enteric viral pathogens among under-5 children in low resource settings - Rina Das; Md. Nasif Hossain; Myron M. Levine; Karen L. Kotloff; Dilruba Nasrin; M. Jahangir Hossain; Richard Omore; Dipika Sur; Tahmeed Ahmed; Robert F. Breiman; A.S.G. Faruque; Matthew C. Freeman (Science of The Total Environment, 2025)

Accumulation of microbial hazards and assessment of food hygiene associated with broiler chicken processing at open air food markets in Maputo, Mozambique - Frederica Lamar; Amélia Mondlane-Milisse; Denise R.A. Brito; Hermógenes N. Mucache; Kelsey J. Jesser; Christine S. Fagnant-Sperati; Courtney Victor; Kayoko Shioda; José M. Fafetine; Joaquim Ângelo Osvaldo Saíde; Eric M. Fèvre; Mia Catharine Mattioli; et al. (International Journal of Food Microbiology, 2025)

Perspective paper: Framework to assess the potential of circular food system technologies - C. Halpern; K. Kennedy Freeman; C.B. Barrett; M. van Dijk; D. Mason-D’Croz; A. Simons; B. van Veen; M. Herrero; H.H.E. Van Zanten (Global Food Security, 2024)

A global systematic review of the cultural ecosystem services provided by wetlands - Kevin A. Wood; Lucy L. Jupe; Francisca C. Aguiar; Alexandra M. Collins; Scott J. Davidson; Will Freeman; Liam Kirkpatrick; Tatiana Lobato-de Magalhães; Emma McKinley; Ana Nuno; Jordi F. Pagès; Antonella Petruzzella; et al. (Ecosystem Services, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Comparison of the reinforcing, antinociceptive, and respiratory depressant effects of prototypical and G-protein biased mu-opioid receptor agonists in male and female Sprague–Dawley rats - C. Austin Zamarripa; Tanya Pareek; Loc M. Pham; Bruce E. Blough; Hayley M. Schrock; Eric J. Vallender; Kenneth J. Sufka; Kevin B. Freeman (Psychopharmacology, 2024)

Age, pair tenure and parenting, but not face identity, predict looking behaviour in a pair-bonded South American primate - Allison R. Lau; Alexander Baxter; Shuyu He; Louise Loyant; Chelsea A. Ortiz-Jimenez; Melissa D. Bauman; Karen L. Bales; Sara M. Freeman (Animal Behaviour, 2024)

Understanding Marsh Elevation and Accretion Processes and Vulnerability to Rising Sea Levels Across Climatic and Geomorphic Gradients in California, USA - Karen M. Thorne; McKenna L. Bristow; Lyndsay L. Rankin; Katya E. Kovalenko; Justine A. Neville; Chase M. Freeman; Glenn R. Guntenspergen (Estuaries and Coasts, 2024)

Sexually selected differences in warbler plumage are related to a putative inversion on the Z chromosome - Peter O. Dunn; Nicholas D. Sly; Corey R. Freeman‐Gallant; Amberleigh E. Henschen; Christen M. Bossu; Kristen C. Ruegg; Piotr Minias; Linda A. Whittingham (Molecular Ecology, 2024)
Large structural variants in the genome, such as inversions, may play an important role in producing population structure and local adaptation to the environment through suppression of recombination. However, relatively few studies have linked inversions to phenotypic traits that are sexually selected and may play a role in reproductive isolation. Here, we found that geographic differences in the sexually selected plumage of a warbler, the common yellowthroat ( Geothlypis trichas ), are largely due to differences in the Z (sex) chromosome (males are ZZ), which contains at least one putative inversion spanning 40% (31/77 Mb) of its length. The inversions on the Z chromosome vary dramatically east and west of the Appalachian Mountains, which provides evidence of cryptic population structure within the range of the most widespread eastern subspecies ( G. t. trichas ). In an eastern (New York) and western (Wisconsin) population of this subspecies, female prefer different male ornaments; larger black facial masks are preferred in Wisconsin and larger yellow breasts are preferred in New York. The putative inversion also contains genes related to vision, which could influence mating preferences. Thus, structural variants on the Z chromosome are associated with geographic differences in male ornaments and female choice, which may provide a mechanism for maintaining different patterns of sexual selection in spite of gene flow between populations of the same subspecies.

A Qualitative Enquiry of On-Farm Rules About Quad Bikes (ATVs): How Rules Are Determined and Implemented at a Farm Level in Rural Australia - Joseph Michael Freeman; Megan Nicole Keatley; Sarah Hui Xin Wong; Anthony M Brown; Emma Louise Webster (Journal of Agromedicine, 2024)

Conversion of rainforest to both traditional and industrial oil palm systems changes the biodiversity, web-building, and prey capture of understory spiders (Liberia, West Africa) - Michael D. Pashkevich; Brogan L. Pett; Cicely A.M. Marshall; Jean-Pierre Caliman; Benedictus Freeman; Marshall M. Guahn; Peter M. Hadfield; Matthew T. Hendren; Morris T. Jah; Tiecanna Jones; Ari Saputra; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2024)

Vaporized nicotine in utero results in reduced birthweight, increased locomotion, and decreased voluntary exercise, dependent on sex and diet in offspring - Samantha L. Penman; Nicole M. Roeder; Jia Wang; Brittany J. Richardson; Ojas Pareek; Lily Freeman-Striegel; Patrick Mohr; Anas Khan; Rina D. Eiden; Saptarshi Chakraborty; Panayotis K. Thanos (Psychopharmacology, 2024)

Review of skeletal carbonate mineralogy of brachiopods with new material from New Zealand - Abigail M. Smith; David F. Freeman; Ian S. Dixon‐Anderson; Daphne E. Lee (New Zealand Journal of Marine and Freshwater Research, 2024)
We combine published and new mineralogical data on most major taxa of brachiopods from all over the world, to investigate patterns and controls on brachiopod carbonate mineralogy. Measurements of 1726 specimens in 162 species (including 56 fossil species) ranged from 79°N to 74°S and from intertidal to almost 4000 m deep. Calcareous brachiopods mostly create strong resilient valves of very low‐Mg calcite ( = 1.3 wt% MgCO 3 ). The substrate‐cemented Craniida ( = 8.9 wt% MgCO 3 ) and Thecideida ( = 6.5 wt% MgCO 3 ) are unusual in precipitating calcite with higher Mg content. This is the first study to find bimineralic brachiopods; a few species show a combination of low‐Mg ( = 0.8 wt% MgCO 3 ) and intermediate‐Mg calcite ( = 7.2 wt% MgCO 3 ) ( sensu Smith AM, Key MM Jr, Gordon DP. 2006. Skeletal mineralogy of bryozoans: taxonomic and temporal patterns. Earth‐Science Reviews. 78:287–306.). While Mg in calcite varies systematically among valve layers and sometimes along the growth axis, we found no consistent difference between valves of the same individual. A weak latitudinal signal indicates some overall temperature control of Mg, but in general, brachiopods are active calcifiers, precipitating low‐Mg calcite even when Mg:Ca ratio in seawater is high. The drivers on brachiopod mineralogy are individual, environmental, and phylogenetic – resulting in complex variability.

Framework for assessing collection-based photocatalytic oxidation systems in HVAC applications for bioaerosol control - Sudharshan Anandan; Andrew J. Fix; Andrew J. Freeman; Lance Miller; Devon P. Scheg; Xavier Morgan; Jae Hong Park; William T. Horton; Ernest R. Blatchley; David M. Warsinger (Building and Environment, 2024)

Comparable foraging effort and habitat use between two geographically proximate tropical seabird colonies - Alice M. Trevail; Sonia Vallocchia; Malcolm A. C. Nicoll; Peter Carr; Stephen C. Votier; Hannah Wood; Robin Freeman (Marine Biology, 2024)
Effective seabird conservation requires understanding their marine spatial ecology. Tracking can reveal details of their foraging ecology and habitat use, as well as the suitability of marine protected areas for at-sea conservation, but results are often regionally specific. Here we characterised the foraging behaviour of tropical breeding brown boobies Sula leucogaster in the Chagos Archipelago, Western Indian Ocean, and tested habitat requirements. GPS tracking of thirteen individuals from two colonies, located 142 km apart on the same atoll (Great Chagos Bank), showed similar foraging effort and habitat preferences despite differences in season and breeding stage. Brown boobies from both tracked populations foraged close to the colony along the atoll shelf edge, avoiding deep oceanic areas and shallow waters of the Great Chagos Bank atoll, but within the Chagos Archipelago Marine Protected Area. Sea-level height anomaly and sea surface temperature were important foraging predictors at both sites, although birds experienced distinct environmental conditions between colonies. These results suggest that while brown boobies have colony-specific at-sea foraging areas, similarities in habitat drivers of distribution and foraging behaviour can inform predictions of distributions at other colonies within the archipelago, with important benefits for at-sea conservation efforts.

Determining aluminium co-ordination of kaolinitic clays before and after calcination with electron energy loss spectroscopy - Alastair T.M. Marsh; Andy P. Brown; Helen M. Freeman; Brant Walkley; Helen Pendlowski; Susan A. Bernal (Applied Clay Science, 2024)

Internal and external factors affect pair mate proximity in captive coyotes, Canis latrans - Alexandra Turano; Stacey P. Brummer; Jeffrey T. Schultz; Julie K. Young; Sara M. Freeman (Animal Behaviour, 2024)

From route to dive: multi-scale habitat selection in a foraging tropical seabird - Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Julia Ramsden; Alice M. Trevail; Hannah Wood; Stephen C. Votier (Marine Biology, 2024)
Comprehending how environmental variability shapes foraging behaviour across habitats is key to unlocking insights into consumer ecology. Seabirds breeding at high latitudes are exemplars of how marine consumers can adapt their behaviours to make use of predictable foraging opportunities, but prey tends to be less predictable in tropical oceanic ecosystems and may require alternative foraging behaviours. Here we used GPS and time-depth recorder loggers to investigate the foraging behaviour of central placed adult red-footed boobies ( Sula sula rubripes ), a tropical seabird that forages in oceanic waters via diving, or by capturing aerial prey such as flying fish in flight. Dive bout dynamics revealed that red-footed boobies appeared to exploit denser, but more sparsely distributed prey patches when diving further from the colony. Furthermore, although we found no evidence of environmentally driven habitat selection along their foraging routes, red-footed boobies preferentially dived in areas with higher sea surface temperatures and chlorophyll-a concentrations compared to conditions along their foraging tracks. This multi-scale variation implies that habitat selection differs between foraging routes compared to dive locations. Finally, red-footed booby dives were deepest during the middle of the day when light penetration was greatest. Ultimately, we highlight the importance of gaining insights into consumer foraging across different ecosystems, thereby broadening understanding of how animals might respond to changing environmental conditions.

Textile dyes as a source of groundwater contamination in Mandalay, Myanmar - Surya M. Freeman; Chit Wityi Oo; Melissa E. Lenczewski; Moe Myint Kyaw (Hydrogeology Journal, 2024)

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

Nitrate exposure from drinking water and dietary sources among Iowa farmers using private wells - Timothy G. Skalaban; Darrin A. Thompson; Jessica M. Madrigal; Benjamin C. Blount; Maria Morel Espinosa; Dana W. Kolpin; Nicole C. Deziel; Rena R. Jones; Laura Beane Freeman; Jonathan N. Hofmann; Mary H. Ward (Science of The Total Environment, 2024)

Cryptic diversification, phenotypic plasticity, and host specialization in a sponge-dwelling goby - Ariel Wang; Sarah Yerrace; Luke Tornabene; Simon J. Brandl; Christopher J. Freeman; Carole C. Baldwin; Jordan M. Casey (Coral Reefs, 2024)

Comprehensive safety assessment of serendipity berry sweet protein produced from Komagataella phaffii - Elaine L. Freeman; Rachel Ward; Mary M. Murphy; Tina Wang; Jason Ryder (Regulatory Toxicology and Pharmacology, 2024)

A toxicological assessment of spermidine trihydrochloride produced using an engineered strain of Saccharomyces cerevisiae - Paola P. Chrysostomou; Elaine L. Freeman; Mary M. Murphy; Rui Pereira; David J. Esdaile; Patrick Keohane (Food and Chemical Toxicology, 2024)

Lack of genotoxicity potential and safety assessment of 4-(2-hydroxyethyl) morpholine present as an impurity in pharmaceuticals and nutritional supplements - Christine Thiffault; Elaine L. Freeman; Gary M. Williams; Nga L. Tran (Food and Chemical Toxicology, 2024)

First molecular identification of the trematode Pulmonicola cochleotrema (Platyhelminthes: Opisthotrematidae) in West Indian manatees (Trichechus manatus, Sirenia: Trichechidae) from Puerto Rico and Florida - Carla I. Rivera-Pérez; Antonio A. Mignucci-Giannoni; Michelle M. Dennis; Mark A. Freeman (Systematic Parasitology, 2024)

Comprehensive Analysis of Coal Combustion Characteristics and Kinetic Parameters of Botswana Coal, Morupule, Mmamabula and Mabesekwa Coalfields - Kamogelo P. Keboletse; Freeman Ntuli; Oluseyi P. Oladijo; Thato Mongalenyane; Gunvor M. Kirkelund; Ana T. Lima (Natural Resources Research, 2023)

Joint associations between established genetic susceptibility loci, pesticide exposures, and risk of prostate cancer - Lauren M. Hurwitz; Laura E. Beane Freeman; Gabriella Andreotti; Jonathan N. Hofmann; Christine G. Parks; Dale P. Sandler; Jay H. Lubin; Jia Liu; Kristine Jones; Sonja I. Berndt; Stella Koutros (Environmental Research, 2023)

Characterization of novel mouse models to study the role of necroptosis in aging and age-related diseases - Ramasamy Selvarani; Hoang Van Michelle Nguyen; Nidheesh Thadathil; Roman F. Wolf; Willard M. Freeman; Christopher D. Wiley; Sathyaseelan S. Deepa; Arlan Richardson (GeroScience, 2023)
To study the impact of necroptosis-induced chronic inflammation on age-related diseases and aging, two knockin mouse models ( Ripk3 -KI and Mlkl -KI) were generated that overexpress two genes involved in necroptosis ( Ripk3 or Mlkl ) when crossed to Cre transgenic mice. Crossing Ripk3 -KI or Mlkl -KI mice to albumin-Cre transgenic mice produced hepatocyte specific hRipk3 -KI or hMlkl -KI mice, which express the two transgenes only in the liver. Ripk3 and Mlkl proteins were overexpressed 10- and fourfold, respectively, in the livers of the hRipk3 -KI or hMlkl -KI mice. Treating young (2-month) hRipk3 -KI or hMlkl -KI mice with carbon tetrachloride (CCl 4 ), a chemical inducer of oxidative stress, resulted in increased necroptosis (Mlkl-oligomers) and inflammation in the liver compared to control mice receiving CCl 4 . Mlkl-oligomerization also was significantly increased in old (18-month) hRipk3 -KI and hMlkl -KI mice compared to old control (Cre negative, Ripk3 -KI and Mlkl -KI) mice. The increase in necroptosis was associated with an increase in inflammation, e.g., inflammatory cytokines (TNFα, IL-6) and macrophage markers (F4/80, CD68). Importantly, steatosis (triglycerides) and fibrosis (e.g., picrosirius red staining, hydroxyproline levels, and transcripts for TGFβ, Col1α1, and Col3α1) that increase with age were significantly higher in the livers of the old hRipk3 -KI or hMlkl -KI mice compared to old control mice. In addition, markers of cellular senescence were significantly increased in the livers of the old hRipk3 -KI and hMlkl -KI mice. Thus, the first mouse models have been developed that allow researchers to study the impact of inducing necroptosis in specific cells/tissues on chronic inflammation in aging and age-related diseases.

Lessons learned from 30-years of operation of the Caernarvon Freshwater Diversion, Louisiana USA - Theryn K. Henkel; Angelina M. Freeman; David C. Lindquist; James W. Pahl; John P. Troutman (Ocean & Coastal Management, 2023)

Correction to: Microglial MHC‑I induction with aging and Alzheimer’s is conserved in mouse models and humans - Collyn M. Kellogg; Kevin Pham; Adeline H. Machalinski; Hunter L. Porter; Harris E. Blankenship; Kyla B. Tooley; Michael B. Stout; Heather C. Rice; Amanda L. Sharpe; Michael J. Beckstead; Ana J. Chucair‑Elliott; Sarah R. Ocañas; et al. (GeroScience, 2023)

Microglial MHC-I induction with aging and Alzheimer’s is conserved in mouse models and humans - Collyn M. Kellogg; Kevin Pham; Adeline H. Machalinski; Hunter L. Porter; Harris E. Blankenship; Kyla B. Tooley; Michael B. Stout; Heather C. Rice; Amanda L. Sharpe; Michael J. Beckstead; Ana J. Chucair-Elliott; Sarah R. Ocañas; et al. (GeroScience, 2023)

Using liquid smoke to control infestations of the ham mite, Tyrophagus putrescentiae, on dry-cured hams during aging - Wenjie Shao; Yan L. Campbell; Thomas W. Phillips; Charles Freeman; Xue Zhang; Jasmine D. Hendrix; K. Virell To; Thu Dinh; William D. Rogers; M. Wes Schilling (Meat Science, 2023)

Modeling identifies variability in SARS-CoV-2 uptake and eclipse phase by infected cells as principal drivers of extreme variability in nasal viral load in the 48 h post infection - Jason Pearson; Timothy Wessler; Alex Chen; Richard C. Boucher; Ronit Freeman; Samuel K. Lai; Raymond Pickles; M. Gregory Forest (Journal of Theoretical Biology, 2023)

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Measurement in the study of human exposure to animal feces: A systematic review and audit - April M. Ballard; Nicholas Laramee; Regine Haardörfer; Matthew C. Freeman; Karen Levy; Bethany A. Caruso (International Journal of Hygiene and Environmental Health, 2023)

Assessing tolerability and physiological responses to 17α-estradiol administration in male rhesus macaques - Michael B. Stout; Kelli L. Vaughan; Jose V. V. Isola; Shivani N. Mann; Bayli Wellman; Jessica M. Hoffman; Hunter L. Porter; Willard M. Freeman; Julie A. Mattison (GeroScience, 2023)

Can a traditional partner preference test quantify monogamous behavior in captive coyotes? - Alexandra Turano; Stacey P. Brummer; Julie K. Young; Sara M. Freeman (Behavioural Processes, 2023)

Energy-effective and low-cost carbon capture from point-sources enabled by water-lean solvents - Yuan Jiang; Paul M. Mathias; Richard F. Zheng; Charlies J. Freeman; Dushyant Barpaga; Deepika Malhotra; Phillip K. Koech; Andy Zwoster; David J. Heldebrant (Journal of Cleaner Production, 2023)

Effectiveness of nets treated with food-grade coatings following various drying methods for controlling mite growth on dry-cured hams - Sadie A. White; Xue Zhang; Yan L. Campbell; Sawyer Wyatt Smith; Thomas W. Phillips; Charles Freeman; M. Wes Schilling (Journal of Stored Products Research, 2023)

Inpatient GHB withdrawal management in an inner-city hospital in Sydney, Australia: a retrospective medical record review - Krista J. Siefried; Georgia Freeman; Darren M. Roberts; Rhiannon Lindsey; Craig Rodgers; Nadine Ezard; Jonathan Brett (Psychopharmacology, 2023)
Rationale Regular consumption of gamma-hydroxybutyrate (GHB) may result in a dependence syndrome that can lead to withdrawal symptoms. There are limited data on medications to manage GHB withdrawal. Objectives To examine characteristics associated with delirium and discharge against medical advice (DAMA), in the context of implementing a GHB withdrawal management protocol at an inner-city hospital in 2020. Methods We retrospectively reviewed records (01 January 2017–31 March 2021), and included admissions that were ≥ 18 years of age, admitted for GHB withdrawal, and with documented recent GHB use. Admissions were assessed for demographics, medications administered, features of delirium, ICU admission, and DAMA. Exploratory analyses were conducted to examine factors associated ( p < 0.2) with features of delirium and DAMA. Results We identified 135 admissions amongst 91 patients. Medications administered included diazepam (133 admissions, 98.5%), antipsychotics (olanzapine [70 admissions, 51.9%]), baclofen (114 admissions, 84%), and phenobarbital (8 admissions, 5.9%). Features of delirium were diagnosed in 21 (16%) admissions. Delirium was associated with higher daily GHB consumption prior to admission, while duration of GHB use, time from presentation to first dose of diazepam, and concomitant methamphetamine use were inversely associated with delirium. DAMA occurred amongst 41 (30%) admissions, and was associated with a longer time from presentation to first dose of baclofen, while being female and receiving a loading dose of diazepam were inversely associated. Conclusions This study adds to the literature in support of the safety and feasibility of diazepam and baclofen for the management of GHB withdrawal. Prospective, randomised trials are required.

Host phylogeny and elevation predict infection by avian haemosporidians in a diverse New Guinean bird community - Geoffrey C. F. Lau; Alexandra M. Class Freeman; Paulo Pulgarín‐R; Carlos Daniel Cadena; Robert E. Ricklefs; Benjamin G. Freeman (Journal of Biogeography, 2023)
Aim The biotic interactions hypothesis predicts that interactions between species are stronger at lower elevations compared to higher elevations. We tested whether this prediction is met by examining elevational patterns in avian haemosporidian infections in New Guinean birds. Location YUS Conservation Area, Papua New Guinea. Taxon Birds and haemosporidia. Methods We collected blood samples from 2268 individuals of 66 bird species along a reef‐to‐ridgetop tropical elevational gradient covering ~3000 m of elevation. We used molecular methods to screen samples for haemosporidian parasites, and sequenced 70% of positive infections to determine the identity of parasite genera. We fit a phylogenetic generalized mixed‐effects model to test whether infection prevalence was higher at low elevations, as predicted by the biotic interactions hypothesis. Finally, we tested for phylogenetic signal in parasite prevalence and in host elevational distribution using Pagel's λ . Results Overall parasite prevalence was 45% . Infection prevalence decreased with elevation, though prevalence remained above ~30% even for high‐elevation communities between 2000 and 3000 m. We found strong phylogenetic signal in infection prevalence, but no phylogenetic signal in host elevational distribution. Nearly all sequenced infections (97%) were of Haemoproteus. Main Conclusions Our results are consistent with predictions arising from the biotic interactions hypothesis. However, phylogenetic relationships among hosts are a much better predictor of infection prevalence than is elevational position: closely related bird species tend to have similar infection prevalence regardless of the elevations where they live.

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Genetic variation in fire recovery and other fire-related traits in a global eucalypt species - Mariano A. Hernández; Jakob B. Butler; Hans Ammitzboll; Jules S. Freeman; Julianne O’Reilly-Wapstra; René E. Vaillancourt; Brad M. Potts (Tree Genetics & Genomes, 2022)
To understand the potential of forests to adapt to wildfire, we studied the genetic architecture of fire-related structural, damage and recovery traits in a globally important Australian forest tree species, Eucalyptus globulus . Fourteen traits were evaluated in an outcrossed F 2 population in a field trial in Tasmania, Australia, which was burnt by a wildfire 14 years after planting. The trial also included open-pollinated families of the grandparental dwarf and tall ecotypes used to produce the F 2 population. We studied the phenotypic correlations within the F 2 population and performed quantitative trait loci (QTL) analyses using a linkage map comprised of 472 markers. Ecotype comparisons revealed that almost all traits were under genetic control, with trees of the dwarf ecotype significantly more damaged and mainly recovering from lignotubers, whereas tall ecotype trees mainly recovered from epicormic resprouts extending for a variable height up the stem. Within the F 2 , tree size was negatively correlated with fire damage and positively correlated with recovery. Genetic control of fire-related traits was confirmed by the detection of 38 QTL in the F 2 population. These QTL accounted for 4 to 43% of the phenotypic variation in these traits. Several QTL co-located and likely reflect pleiotropic effects. However, many independent QTL were detected, including QTL for crown consumption and trunk scorch, epicormic resprouting, resprout herbivory, and seedling establishment. The QTL detected argue that many genetically controlled mechanisms are responsible for variation in fire damage and recovery.

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Differential Regulation of Mouse Hippocampal Gene Expression Sex Differences by Chromosomal Content and Gonadal Sex - Sarah R. Ocañas; Victor A. Ansere; Kyla B. Tooley; Niran Hadad; Ana J. Chucair-Elliott; David R. Stanford; Shannon Rice; Benjamin Wronowski; Kevin D. Pham; Jessica M. Hoffman; Steven N. Austad; Michael B. Stout; et al. (Molecular Neurobiology, 2022)

Correction to: The CannTeen study: verbal episodic memory, spatial working memory, and response inhibition in adolescent and adult cannabis users and age‑matched controls - W. Lawn; N. Fernandez‑Vinson; C. Mokrysz; G. Hogg; R. Lees; K. Trinci; K. Petrilli; A. Borissova; S. Ofori; S. Waters; P. Michór; M. B. Wall; et al. (Psychopharmacology, 2022)

Integrating Pore-Scale Flow MRI and X-ray μCT for Validation of Numerical Flow Simulations in Porous Sedimentary Rocks - K. Karlsons; D. W. de Kort; F. O. Alpak; J. Dietderich; J. J. Freeman; M. Appel; M. D. Mantle; A. J. Sederman; L. F. Gladden (Transport in Porous Media, 2022)
Single-phase fluid flow velocity maps in Ketton and Estaillades carbonate rock core plugs are computed at a pore scale, using the lattice Boltzmann method (LBM) simulations performed directly on three-dimensional (3D) X-ray micro-computed tomography (µCT) images (≤ 7 µm spatial resolution) of the core plugs. The simulations are then benchmarked on a voxel-by-voxel and pore-by-pore basis to quantitative, 3D spatially resolved magnetic resonance imaging (MRI) flow velocity maps, acquired at 35 µm isotropic spatial resolution for flow of water through the same rock samples. Co-registration of the 3D experimental and simulated velocity maps and coarse-graining of the simulation to the same resolution as the experimental data allowed the data to be directly compared. First, the results are demonstrated for Ketton limestone rock, for which good qualitative and quantitative agreement was found between the simulated and experimental velocity maps. The flow-carrying microstructural features in Ketton rock are mostly larger than the spatial resolution of the µCT images, so that the segmented images are an adequate representation of the pore space. Second, the flow data are presented for Estaillades limestone, which presents a more heterogeneous case with microstructural features below the spatial resolution of the µCT images. Still, many of the complex flow patterns were qualitatively reproduced by the LBM simulation in this rock, although in some pores, noticeable differences between the LBM and MRI velocity maps were observed. It was shown that 80% of the flow (fractional summed z -velocities within pores) in the Estaillades rock sample is carried by just 10% of the number of macropores, which is an indication of the high structural heterogeneity of the rock; in the more homogeneous Ketton rock, 50% of the flow is carried by 10% of the macropores. By analysing the 3D MRI velocity map, it was found that approximately one-third of the total flow rate through the Estaillades rock is carried by microporosity—a porosity that is not captured at the spatial resolution of the µCT image.

Patterns of genomic diversity and linkage disequilibrium across the disjunct range of the Australian forest tree Eucalyptus globulus - Jakob B. Butler; Jules S. Freeman; Brad M. Potts; René E. Vaillancourt; Hossein V. Kahrood; Peter K. Ades; Philippe Rigault; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2022)
The evolutionary trajectory of a population both influences and is influenced by characteristics of its genome. A disjunct population, for example is likely to exhibit genomic features distinct from those of continuous populations, reflecting its specific evolutionary history and influencing future recombination outcomes. We examined genetic diversity, population differentiation and linkage disequilibrium (LD) across the highly disjunct native range of the Australian forest tree Eucalyptus globulus , using 203,337 SNPs genotyped in 136 trees spanning seven races. We found support for four broad genetic groups, with moderate F ST , high allelic diversity and genome-wide LD decaying to an r 2 of 0.2 within 4 kb on average. These results are broadly similar to those reported previously in Eucalyptus species and support the ‘ring’ model of migration proposed for E. globulus . However, two of the races (Otways and South-eastern Tasmania) exhibited a much slower decay of LD with physical distance than the others and were also the most differentiated and least diverse, which may reflect the effects of selective sweeps and/or genetic bottlenecks experienced in their evolutionary history. We also show that F ST and rates of LD vary within and between chromosomes across all races, suggestive of recombination outcomes influenced by genomic features, hybridization or selection. The results obtained from studying this species serve to illustrate the genomic effects of population disjunction and further contribute to the characterisation of genomes of woody genera.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The CannTeen study: verbal episodic memory, spatial working memory, and response inhibition in adolescent and adult cannabis users and age-matched controls - W. Lawn; N. Fernandez-Vinson; C. Mokrysz; G. Hogg; R. Lees; K. Trinci; K. Petrilli; A. Borissova; S. Ofori; S. Waters; P. Michór; M. B. Wall; et al. (Psychopharmacology, 2022)
Background Preclinical and human studies suggest that adolescent cannabis use may be associated with worse cognitive outcomes than adult cannabis use. We investigated the associations between chronic cannabis use and cognitive function in adolescent and adult cannabis users and controls. We hypothesised user-status would be negatively associated with cognitive function and this relationship would be stronger in adolescents than adults. Methods As part of the ‘CannTeen’ project, this cross-sectional study assessed cognitive performance in adolescent cannabis users ( n = 76; 16–17-year-olds), adolescent controls ( n = 63), adult cannabis users ( n = 71; 26–29-year-olds) and adult controls ( n = 64). Users used cannabis 1–7 days/week. Adolescent and adult cannabis users were matched on cannabis use frequency (4 days/week) and time since last use (2.5 days). Verbal episodic memory (VEM) was assessed using the prose recall task, spatial working memory (SWM) was assessed using the spatial n-back task, and response inhibition was assessed with the stop-signal task. Primary outcome variables were: delayed recall, 3-back discriminability, and stop signal reaction time, respectively. Results Users had worse VEM than controls ( F (1,268) = 7.423, p = 0.007). There were no significant differences between user-groups on SWM or response inhibition. Null differences were supported by Bayesian analyses. No significant interactions between age-group and user-group were found for VEM, SWM, or response inhibition. Conclusions Consistent with previous research, there was an association between chronic cannabis use and poorer VEM, but chronic cannabis use was not associated with SWM or response inhibition. We did not find evidence for heightened adolescent vulnerability to cannabis-related cognitive impairment.

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Using Decision Analysis to Integrate Habitat and Community Values for Coastal Resilience Planning - David M. Martin; Jackie A. Specht; Michelle R. Canick; Kelly L. Leo; Kathleen Freeman (Estuaries and Coasts, 2022)
Decision analysis is applied to habitat and community resilience planning in Maryland, USA. Sea level rise is causing wetland loss and increased flooding in coastal areas. A team at The Nature Conservancy analyzed a decision to identify high-value conservation planning units across Maryland’s Lower Eastern Shore. The team selected two fundamental objectives: minimize habitat loss and minimize community flood impacts. Sub-objectives included habitat function, habitat migration potential, critical infrastructure, and social vulnerability. Spatial attributes were selected based on ecological knowledge about habitat and socio-economic knowledge about sustaining populations in flood-prone areas. Seven planning units were developed across the Lower Eastern Shore. Single-attribute value functions determined the overall value of each unit per attribute, whereas multi-attribute value functions determined the overall value of each unit for all fundamental objectives. Sensitivity analysis incorporated data adjustments based on different flood scenarios and unit sizes, and variation in attribute weights associated with the multi-attribute value function. The Pareto efficiency principle revealed tradeoffs between units for habitat protection and management and community engagement and adaptation. Results indicate that four units are Pareto efficient under different sensitivity iterations and they trade off value in the fundamental objectives, whereas one unit provides the highest combined habitat and community value. This research guided thinking about equity in decision making and targeting conservation actions at local scales. The approach and methods can be used to inform conservation decisions in other similar contexts.

The precautionary principle and dietary DNA metabarcoding: Commonly used abundance thresholds change ecological interpretation - Bethan L. Littleford‐Colquhoun; Patrick T. Freeman; Violet I. Sackett; Camille V. Tulloss; Lauren M. McGarvey; Chris Geremia; Tyler R. Kartzinel (Molecular Ecology, 2022)
Dietary DNA metabarcoding enables researchers to identify and characterize trophic interactions with a high degree of taxonomic precision. It is also sensitive to sources of bias and contamination in the field and laboratory. One of the earliest and most common strategies for dealing with such sensitivities has been to remove all low‐abundance sequences and conduct ecological analyses based on the presence or absence of food taxa. Although this step is now often perceived to be necessary, evidence of its sufficiency is lacking and more attention to the risk of introducing other errors is needed. Using computer simulations, we demonstrate that common strategies to remove low‐abundance sequences can erroneously eliminate true dietary sequences in ways that impact downstream inferences. Using real data from well‐studied wildlife populations in Yellowstone National Park, we further show how these strategies can markedly alter the composition of dietary profiles in ways that scale‐up to obscure ecological interpretations about dietary generalism, specialism, and composition. Although the practice of removing low‐abundance sequences may continue to be a useful strategy to address research questions that focus on a subset of relatively abundant foods, its continued widespread use risks generating misleading perceptions about the structure of trophic networks. Researchers working with dietary DNA metabarcoding data—or similar data such as environmental DNA, microbiomes, or pathobiomes—should be aware of drawbacks and consider alternative bioinformatic, experimental, and statistical solutions.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

The kappa-opioid receptor agonist, triazole 1.1, reduces oxycodone self-administration and enhances oxycodone-induced thermal antinociception in male rats - C. Austin Zamarripa; Tanya Pareek; Hayley M. Schrock; Thomas E. Prisinzano; Bruce E. Blough; Kenneth J. Sufka; Kevin B. Freeman (Psychopharmacology, 2021)

Machine Learning Can Assign Geologic Basin to Produced Water Samples Using Major Ion Geochemistry - Jenna L. Shelton; Aaron M. Jubb; Samuel W. Saxe; Emil D. Attanasi; Alexei V. Milkov; Mark Engle; Philip A. Freeman; Christopher A. Shaffer; Madalyn S. Blondes (Natural Resources Research, 2021)
Understanding the geochemistry of waters produced during petroleum extraction is essential to informing the best treatment and reuse options, which can potentially be optimized for a given geologic basin. Here, we used the US Geological Survey’s National Produced Waters Geochemical Database (PWGD) to determine if major ion chemistry could be used to classify accurately a produced water sample to a given geologic basin based on similarities to a given training dataset. Two datasets were derived from the PWGD: one with seven features but more samples (PWGD7), and another with nine features but fewer samples (PWGD9). The seven-feature dataset, prior to randomly generating a training and testing (i.e., validation) dataset, had 58,541 samples, 20 basins, and was classified based on total dissolved solids (TDS), bicarbonate (HCO 3 ), Ca, Na, Cl, Mg, and sulfate (SO 4 ). The nine-feature dataset, prior to randomly splitting into a training and testing (i.e., validation) dataset, contained 33,271 samples, 19 basins, and was classified based on TDS, HCO 3 , Ca, Na, Cl, Mg, SO 4 , pH, and specific gravity. Three supervised machine learning algorithms—Random Forest, k-Nearest Neighbors, and Naïve Bayes—were used to develop multi-class classification models to predict a basin of origin for produced waters using major ion chemistry. After training, the models were tested on three different datasets: Validation7, Validation9, and one based on data absent from the PWGD. Prediction accuracies across the models ranged from 23.5 to 73.5% when tested on the two PWGD-based datasets. A model using the Random Forest algorithm predicted most accurately compared to all other models tested. The models generally predicted basin of origin more accurately on the PWGD7-based dataset than on the PWGD9-based dataset. An additional dataset, which contained data not in the PWGD, was used to test the most accurate model; results suggest that some basins may lack geochemical diversity or may not be well described, while others may be geochemically diverse or are well described. A compelling result of this work is that a produced water basin of origin can be determined using major ions alone and, therefore, deep basinal fluid compositions may not be as variable within a given basin as previously thought. Applications include predicting the geochemistry of produced fluid prior to drilling at different intervals and assigning historical produced water data to a producing basin.

The importance of transitions for hatching success and brood mortality in the barnacle Chthamalus fragilis under laboratory conditions - Paul H. Dunn; Brennan N. Fitzgerald; M. Chase Freeman (Hydrobiologia, 2021)

Bivalve Feeding on the Brown Tide Aureoumbra lagunensis in a Shallow Coastal Environment - Eve Galimany; Jessica Lunt; Christopher J. Freeman; I. Segura-García; M. Mossop; A. Domingos; J. Houk; Valerie J. Paul (Frontiers in Marine Science, 2021)
Brown tides formed by Aureoumbra lagunensis decrease light penetration in the water column and are often followed by hypoxic events that result in the loss of fish and shellfish. To understand the ability of bivalve filter feeders to control and prevent A. lagunensis blooms, we exposed eastern oysters ( Crassostrea virginica ), hooked mussels ( Ischadium recurvum ), and hard clams ( Mercenaria mercenaria ) to a naturally co-occurring brown tide in the Indian River Lagoon (IRL), Florida, United States. Bivalves were exposed in the laboratory to multiple concentrations (10 4 to 10 6 cells mL –1 ) of isotopically labeled ( 13 C and 15 N) A. lagunensis cells. The standard clearance rate (herein clearance rate) of each bivalve species was calculated using flow cytometry to quantify A. lagunensis cell removal. The highest clearance rates were at 10 4 cells mL –1 , but values varied across bivalve species (2.16 ± 0.30, 3.03 ± 0.58, and 0.41 ± 0.12 L h –1 for C. virginica , I. recurvum , and M. mercenaria , respectively). Although clearance rates decreased with increasing bloom concentrations, bivalves were still consuming algal cells at all concentrations and were retaining and assimilating more cells at the highest concentrations, as revealed by δ 13 C and δ 15 N values. We highlight interspecific differences among bivalve species in the removal of A. lagunensis , supporting the importance of healthy and diverse filter feeding communities in estuaries, especially as threats of brown tides and other HABs are increasing in the Anthropocene.

Oklahoma Nathan Shock Aging Center — assessing the basic biology of aging from genetics to protein and function - Holly Van Remmen; Willard M. Freeman; Benjamin F. Miller; Michael Kinter; Jonathan D. Wren; Ann Chiao; Rheal A. Towner; Timothy A. Snider; William E. Sonntag; Arlan Richardson (GeroScience, 2021)

Multiscale Digital Rock Analysis for Complex Rocks - L. C. Ruspini; P. E. Øren; S. Berg; S. Masalmeh; T. Bultreys; C. Taberner; T. Sorop; F. Marcelis; M. Appel; J. Freeman; O. B. Wilson (Transport in Porous Media, 2021)

Intensity of grass invasion negatively correlated with population density and age structure of an endangered dune plant across its range - Scott F. Jones; Anna Kennedy; Chase M. Freeman; Karen M. Thorne (Biological Invasions, 2021)

Modelling potential Pleistocene habitat corridors between Afromontane forest regions - Kaitlin E. Allen; Walter P. Tapondjou; Benedictus Freeman; Jacob C. Cooper; Rafe M. Brown; A. Townsend Peterson (Biodiversity and Conservation, 2021)

Assessing awareness on biodiversity conservation among Nigerians: the Aichi Biodiversity Target 1 - Emmanuel O. Akindele; Michael C. Ekwemuka; Paul Apeverga; Tajudeen O. Amusa; Samuel Olajuyigbe; Oluwakayode M. Coker; Fatsuma Olaleru; Michelle Fasona; Elizabeth N. Usen; Abubakar S. Ringim; Opeyemi A. Adedoja; Chinedu C. Nsude; et al. (Biodiversity and Conservation, 2021)

Climate change impacts on human health at an actionable scale: a state-level assessment of Indiana, USA - G. M. Filippelli; J. L. Freeman; J. Gibson; S. Jay; M. J. Moreno-Madriñán; I. Ogashawara; F. S. Rosenthal; Y. Wang; E. Wells (Climatic Change, 2020)

Potential Environmental Effects of Marine Renewable Energy Development—The State of the Science - Andrea E. Copping; Lenaïg G. Hemery; Dorian M. Overhus; Lysel Garavelli; Mikaela C. Freeman; Jonathan M. Whiting; Alicia M. Gorton; Hayley K. Farr; Deborah J. Rose; Levy G. Tugade (Journal of Marine Science and Engineering, 2020)
Marine renewable energy (MRE) harnesses energy from the ocean and provides a low-carbon sustainable energy source for national grids and remote uses. The international MRE industry is in the early stages of development, focused largely on tidal and riverine turbines, and wave energy converters (WECs), to harness energy from tides, rivers, and waves, respectively. Although MRE supports climate change mitigation, there are concerns that MRE devices and systems could affect portions of the marine and river environments. The greatest concern for tidal and river turbines is the potential for animals to be injured or killed by collision with rotating blades. Other risks associated with MRE device operation include the potential for turbines and WECs to cause disruption from underwater noise emissions, generation of electromagnetic fields, changes in benthic and pelagic habitats, changes in oceanographic processes, and entanglement of large marine animals. The accumulated knowledge of interactions of MRE devices with animals and habitats to date is summarized here, along with a discussion of preferred management methods for encouraging MRE development in an environmentally responsible manner. As there are few devices in the water, understanding is gained largely from examining one to three MRE devices. This information indicates that there will be no significant effects on marine animals and habitats due to underwater noise from MRE devices or emissions of electromagnetic fields from cables, nor changes in benthic and pelagic habitats, or oceanographic systems. Ongoing research to understand potential collision risk of animals with turbine blades still shows significant uncertainty. There has been no significant field research undertaken on entanglement of large animals with mooring lines and cables associated with MRE devices.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Molecular changes in transcription and metabolic pathways underlying muscle atrophy in the CuZnSOD null mouse model of sarcopenia - Kavithalakshmi Sataranatarajan; Gavin Pharaoh; Jacob L. Brown; Rojina Ranjit; Katarzyna M. Piekarz; Kaitlyn Street; Jonathan D. Wren; Constantin Georgescu; Caroline Kinter; Michael Kinter; Willard M. Freeman; Arlan Richardson; et al. (GeroScience, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Fruits, vegetables, and health: A comprehensive narrative, umbrella review of the science and recommendations for enhanced public policy to improve intake - Taylor C. Wallace; Regan L. Bailey; Jeffrey B. Blumberg; Britt Burton-Freeman; C-y. Oliver Chen; Kristi M. Crowe-White; Adam Drewnowski; Shirin Hooshmand; Elizabeth Johnson; Richard Lewis; Robert Murray; Sue A. Shapses; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Quantification of observable behaviors induced by typical and atypical kappa-opioid receptor agonists in male rhesus monkeys - S. L. Huskinson; D. M. Platt; M. Brasfield; M. E. Follett; T. E. Prisinzano; B. E. Blough; K. B. Freeman (Psychopharmacology, 2020)

Meningitis associated with dracunculid nematodes in a spotted eagle ray ( Aetobatus narinari ) - Michelle M. Dennis; Jun Wei Alric Yeow; Brittani Nicolaci; Saundra H. Sample; Mark A. Freeman (Journal of Fish Diseases, 2020)

Risk Retirement—Decreasing Uncertainty and Informing Consenting Processes for Marine Renewable Energy Development - Andrea E. Copping; Mikaela C. Freeman; Alicia M. Gorton; Lenaïg G. Hemery (Journal of Marine Science and Engineering, 2020)
Marine renewable energy (MRE) is under development in many coastal nations, adding to the portfolio of low carbon energy sources that power national electricity grids as well as off-grid uses in isolated areas and at sea. Progress in establishing the MRE industry, largely wave and tidal energy, has been slowed in part due to uncertainty about environmental risks of these devices, including harm to marine animals and habitats, and the associated concerns of regulators and stakeholders. A process for risk retirement was developed to organize and apply knowledge in a strategic manner that considered whether specific environmental effects are likely to cause harm. The risk retirement process was tested against two key MRE stressors: effects of underwater noise from operational MRE devices on marine animals, and effects of electromagnetic fields from MRE electrical export cables on marine animals. The effects of installation of MRE devices were not accounted for in this analysis. Applying the risk retirement process could decrease the need for costly investigations of each potential effect at every new MRE project site and help move the industry beyond current barriers.

High interannual variability of a climate-driven amphibian community in a seasonal rainforest - Nicolas Dubos; Loïs Morel; Angelica Crottini; Karen Freeman; Jean Honoré; Honoré Lava; Jean Noël; Ingrid Porton; Georges Rendrirendry; Gonçalo M. Rosa; Franco Andreone (Biodiversity and Conservation, 2020)

Effects of Mowing and Prescribed Fire on Plant Community Structure and Function in Rare Coastal Sandplains, Nantucket Island, MA, USA - Helen Mills Poulos; Rachael S. Freeman; Jennifer M. Karberg; Karen C. Beattie; Danielle I. O’Dell; Kelly A. Omand (Environmental Management, 2020)

Raising young with limited resources: supplementation improves body condition and advances fledging of Canada Jays - Nikole E. Freeman; D. Ryan Norris; Alex O. Sutton; Amy E. M. Newman (Ecology, 2020)
Food availability early in life can play a vital role in an individual's development and success, but experimental evidence for the direct effects of food on body condition, physiology, and survival of young animals in the wild is still relatively scarce. Food‐caching Canada Jays ( Perisoreus canadensis ) begin breeding in the late winter and, therefore, rely on either cached food or seemingly limited quantities of fresh food to feed nestlings in the early spring. Using a 2‐yr food supplementation experiment conducted during the nestling period and 40 yr of observational data on food supplemented by the public, we examined whether food quantity during early life influenced the physiology, body condition, timing of fledging, and survival of young Canada Jays in Algonquin Provincial Park, Ontario, Canada . Experimental food supplementation of breeding pairs advanced the fledging date of young by 24% (5.5 d) compared to controls. In 1 yr of the experiment, nestlings raised on experimentally supplemented territories had lower feather corticosterone concentrations and were in higher body condition than controls. Across treatment and control nests, young that successfully fledged had lower concentrations of feather corticosterone and were in higher body condition than those that did not fledge. Based on 40 yr of observational data, nestling body condition was positively related to the degree of food supplementation by park visitors and nestlings in higher body condition were more likely to be observed in the population in the following fall. Our results demonstrate how food availability early in life can have important downstream consequences on metrics related to individual fitness, including first year survival.

Impacts of Urbanization and Development on Estuarine Ecosystems and Water Quality - Lauren A. Freeman; D. Reide Corbett; Allison M. Fitzgerald; Daniel A. Lemley; Antonietta Quigg; Cecily N. Steppe (Estuaries and Coasts, 2019)

Independent QTL underlie resistance to the native pathogen Quambalaria pitereka and the exotic pathogen Austropuccinia psidii in Corymbia - Jakob B. Butler; Brad M. Potts; René E. Vaillancourt; David J. Lee; Geoff S. Pegg; Jules S. Freeman (Tree Genetics & Genomes, 2019)

Tamoxifen induction of Cre recombinase does not cause long-lasting or sexually divergent responses in the CNS epigenome or transcriptome: implications for the design of aging studies - Ana J. Chucair-Elliott; Sarah R. Ocanas; David R. Stanford; Niran Hadad; Benjamin Wronowski; Laura Otalora; Michael B. Stout; Willard M. Freeman (GeroScience, 2019)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

Cancer incidence in the Agricultural Health Study after 20 years of follow-up - Catherine C. Lerro; Stella Koutros; Gabriella Andreotti; Dale P. Sandler; Charles F. Lynch; Lydia M. Louis; Aaron Blair; Christine G. Parks; Srishti Shrestha; Jay H. Lubin; Paul S. Albert; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2019)

Soil organic carbon stability in forests: Distinct effects of tree species identity and traits - Gerrit Angst; Kevin E. Mueller; David M. Eissenstat; Susan Trumbore; Katherine H. Freeman; Sarah E. Hobbie; Jon Chorover; Jacek Oleksyn; Peter B. Reich; Carsten W. Mueller (Global Change Biology, 2019)
Rising atmospheric CO 2 concentrations have increased interest in the potential for forest ecosystems and soils to act as carbon (C) sinks. While soil organic C contents often vary with tree species identity, little is known about if, and how, tree species influence the stability of C in soil. Using a 40 year old common garden experiment with replicated plots of eleven temperate tree species, we investigated relationships between soil organic matter (SOM) stability in mineral soils and 17 ecological factors (including tree tissue chemistry, magnitude of organic matter inputs to the soil and their turnover, microbial community descriptors, and soil physicochemical properties). We measured five SOM stability indices, including heterotrophic respiration, C in aggregate occluded particulate organic matter (POM) and mineral associated SOM, and bulk SOM δ 15 N and ∆ 14 C. The stability of SOM varied substantially among tree species, and this variability was independent of the amount of organic C in soils. Thus, when considering forest soils as C sinks, the stability of C stocks must be considered in addition to their size. Further, our results suggest tree species regulate soil C stability via the composition of their tissues, especially roots. Stability of SOM appeared to be greater (as indicated by higher δ 15 N and reduced respiration) beneath species with higher concentrations of nitrogen and lower amounts of acid insoluble compounds in their roots, while SOM stability appeared to be lower (as indicated by higher respiration and lower proportions of C in aggregate occluded POM) beneath species with higher tissue calcium contents. The proportion of C in mineral associated SOM and bulk soil ∆ 14 C, though, were negligibly dependent on tree species traits, likely reflecting an insensitivity of some SOM pools to decadal scale shifts in ecological factors. Strategies aiming to increase soil C stocks may thus focus on particulate C pools, which can more easily be manipulated and are most sensitive to climate change.

Pre-diagnostic carbohydrate intake and treatment failure after radical prostatectomy for early-stage prostate cancer - Kyeezu Kim; Angela Kong; Robert C. Flanigan; Marcus L. Quek; Courtney M. P. Hollowell; Patricia P. Vidal; Jefferey Branch; Leslie A. Dean; Virgilia Macias; Andre A. Kajadacsy-Balla; Marian L. Fitzgibbon; Daisy Cintron; et al. (Cancer Causes & Control, 2019)

The buzz segment of Savannah sparrow song is a population marker - Heather Williams; Clint W. Robins; D. Ryan Norris; Amy E. M. Newman; Corey R. Freeman-Gallant; Nathaniel T. Wheelwright; Daniel J. Mennill (Journal of Ornithology, 2019)

Picket-fences in the plasma membrane: functions in immune cells and phagocytosis - Sivakami M. Mylvaganam; Sergio Grinstein; Spencer A. Freeman (Seminars in Immunopathology, 2018)

Expanding, shifting and shrinking: The impact of global warming on species’ elevational distributions - Benjamin G. Freeman; Julie A. Lee‐Yaw; Jennifer M. Sunday; Anna L. Hargreaves (Global Ecology and Biogeography, 2018)
Aim Species are responding to climate warming by shifting their distributions toward historically cooler regions, but the degree to which expansions at cool range limits are balanced by contractions at warm limits is unknown. We synthesized published data documenting shifts at species’ warm versus cool range limits along elevational gradients to (a) test classic ecological theory that predicts temperature more directly influences species’ cool range limits than their warm range limits, and (b) determine how warming‐associated shifts have changed the extent and area of species’ elevational distributions. Location Global. Time period 1802–2012. Major taxa studied Vascular plants, endotherms, ectotherms. Methods We compiled a dataset of 975 species from 32 elevational gradients for which range shifts have been measured at both warm and cool range limits. We compared the magnitude and variance of shifts at species’ warm versus cool limits, and quantified how range shifts have impacted species’ elevational extents and areas. Results On average species have shifted upslope associated with temperature increases at both warm and cool limits (warm limit: 92 ± 455 m/C; cool limit: 131 ± 465 m/C; overall mean ± SD ). There was no systematic difference in the magnitude or variance of shifts at warm versus cool limits and thus no indication that cool limits are more directly controlled by temperature. Species’ elevational extents and available area significantly decreased for mountaintop species. Main conclusions Our results do not support the long‐standing hypothesis that cool limits are more sensitive or responsive to temperature. We find that, across the globe, mountaintop species’ ranges are significantly shrinking as they shift upslope, supporting predictions that high elevation species are especially vulnerable to temperature increases. Our synthesis highlights the extreme variation in species’ distributional responses to warming, which may indicate that biotic interactions play a more prominent role in setting range limits than previously thought.

Limited support for the “abundant centre” hypothesis in birds along a tropical elevational gradient: implications for the fate of lowland tropical species in a warmer future - Benjamin G. Freeman; Bruce M. Beehler (Journal of Biogeography, 2018)
Aim Since Darwin, ecologists have assumed that species tend to be abundant in the centre of their geographic distributions and rare at their range edges. We test two predictions of this abundant centre hypothesis: (a) that species are common in the centre of their range and rare at the edges and (b) that empirical distributions along environmental gradients are well described by symmetric bell‐shaped curves. Location A reef‐to‐ridgetop elevational gradient in the Yopno–Urawa–Som Conservation Area ( YUS CA ) on the Huon Peninsula in Papua New Guinea. Taxon Birds. Methods We use mist net capture rates to quantify species’ abundances as a function of range position, then fit a series of models with different shapes, including symmetric curves, to species’ empirical abundance distributions. Results Species peak abundances were located near species’ low elevation range edges, high elevation range edges and everywhere in between. Real abundance distributions were fit well by symmetric curves in fewer than half of the species we analysed. Most lowland species have high abundances at their low elevation margin near sea level. Main conclusions We find only limited support for the abundant centre hypothesis. Most lowland species appear to currently occupy a “truncated” realized niche, suggesting that they will be able to persist at low elevations even as temperatures increase and that lowland biotic attrition is unlikely. In addition to analyses, we present (a) a full species list for the 256 species recorded thus far within the YUS CA , with elevational limits for all forest species and (b) the raw data from our extensive mist net surveys. This information provides valuable baseline data that can be used by future biodiversity scientists to evaluate the changes in the YUS avifauna and will be generally useful to biodiversity scientists studying tropical elevational gradients.

Global change‐driven effects on dissolved organic matter composition: Implications for food webs of northern lakes - Irena F. Creed; Ann‐Kristin Bergström; Charles G. Trick; Nancy B. Grimm; Dag O. Hessen; Jan Karlsson; Karen A. Kidd; Emma Kritzberg; Diane M. McKnight; Erika C. Freeman; Oscar E. Senar; Agneta Andersson; et al. (Global Change Biology, 2018)
Northern ecosystems are experiencing some of the most dramatic impacts of global change on Earth. Rising temperatures, hydrological intensification, changes in atmospheric acid deposition and associated acidification recovery, and changes in vegetative cover are resulting in fundamental changes in terrestrial–aquatic biogeochemical linkages. The effects of global change are readily observed in alterations in the supply of dissolved organic matter ( DOM )—the messenger between terrestrial and lake ecosystems—with potentially profound effects on the structure and function of lakes. Northern terrestrial ecosystems contain substantial stores of organic matter and filter or funnel DOM , affecting the timing and magnitude of DOM delivery to surface waters. This terrestrial DOM is processed in streams, rivers, and lakes, ultimately shifting its composition, stoichiometry, and bioavailability. Here, we explore the potential consequences of these global change‐driven effects for lake food webs at northern latitudes. Notably, we provide evidence that increased allochthonous DOM supply to lakes is overwhelming increased autochthonous DOM supply that potentially results from earlier ice‐out and a longer growing season. Furthermore, we assess the potential implications of this shift for the nutritional quality of autotrophs in terms of their stoichiometry, fatty acid composition, toxin production, and methylmercury concentration, and therefore, contaminant transfer through the food web. We conclude that global change in northern regions leads not only to reduced primary productivity but also to nutritionally poorer lake food webs, with discernible consequences for the trophic web to fish and humans.

Counterintuitive migration patterns by Atlantic salmon Salmo salar smolts in a large lake - Hannele M. Honkanen; Jessica R. Rodger; Alastair Stephen; Keith Adams; James Freeman; Colin E. Adams (Journal of Fish Biology, 2018)
What little is known about the seaward migration of Salmo salar smolt migration through standing waters indicates that it is both slow and results in high mortality rates, compared with riverine migration. This may be partly because smolts in lakes need to swim more actively and require more complex directional cues than they do in rivers. In this telemetry study of smolt migration through Loch Lomond, S. salar smolts made repeated movements in directions away from the outflowing river, which considerably increased migration time.

Analysis of DNA modifications in aging research - Dustin R. Masser; Niran Hadad; Hunter Porter; Michael B. Stout; Archana Unnikrishnan; David R. Stanford; Willard M. Freeman (GeroScience, 2018)

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Role of DNA methylation in the dietary restriction mediated cellular memory - Archana Unnikrishnan; Jordan Jackson; Stephanie A. Matyi; Niran Hadad; Benjamin Wronowski; Constantin Georgescu; Karla P. Garrett; Jonathan D. Wren; Willard M. Freeman; Arlan Richardson (GeroScience, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Invasive Asian Fusarium – Euwallacea ambrosia beetle mutualists pose a serious threat to forests, urban landscapes and the avocado industry - Kerry O’Donnell; Ran Libeskind-Hadas; Jiri Hulcr; Craig Bateman; Matthew T. Kasson; Randy C. Ploetz; Joshua L. Konkol; Jill N. Ploetz; Daniel Carrillo; Alina Campbell; Rita E. Duncan; Pradeepa N. H. Liyanage; et al. (Phytoparasitica, 2016)

Constructed wetlands may lower inorganic nutrient inputs but enhance DOC loadings into a drinking water reservoir in North Wales - C. Scholz; T. G. Jones; M. West; A. M. S. Ehbair; C. Dunn; C. Freeman (Environmental Science and Pollution Research, 2016)

Evidence for different QTL underlying the immune and hypersensitive responses of Eucalyptus globulus to the rust pathogen Puccinia psidii - J. B. Butler; J. S. Freeman; R. E. Vaillancourt; B. M. Potts; M. Glen; D. J. Lee; G. S. Pegg (Tree Genetics & Genomes, 2016)

Branch Width and Height Influence the Incorporation of Branches into Foraging Trails and Travel Speed in Leafcutter Ants Atta cephalotes (L.) (Hymenoptera: Formicidae) - B M Freeman; J Chaves-Campos (Neotropical Entomology, 2016)

Fruit Polyphenols: A Review of Anti-inflammatory Effects in Humans - Shama V. Joseph; Indika Edirisinghe; Britt M. Burton-Freeman (Critical Reviews in Food Science and Nutrition, 2016)

Temporal shifts in activity of prey following large predator reintroductions - Craig J. Tambling; Liaan Minnie; Jordana Meyer; Elizabeth W. Freeman; Rachel M. Santymire; John Adendorff; Graham I. H. Kerley (Behavioral Ecology and Sociobiology, 2015)

Field-Scale Simulation of Production from Oceanic Gas Hydrate Deposits - Matthew T. Reagan; George J. Moridis; Jeffery N. Johnson; Lehua Pan; Craig M. Freeman; Lehua Pan; Katie L. Boyle; Noel D. Keen; Jarle Husebo (Transport in Porous Media, 2015)

Comparison of trends in butterfly populations between monitoring schemes - D. B. Roy; E. F. Ploquin; Z. Randle; K. Risely; M. S. Botham; I. Middlebrook; D. Noble; K. Cruickshanks; S. N. Freeman; T. M. Brereton (Journal of Insect Conservation, 2015)

Pharmacokinetics and Efficacy of the Spleen Tyrosine Kinase Inhibitor R406 after Ocular Delivery for Retinoblastoma - Eleanor M. Pritchard; Elizabeth Stewart; Fangyi Zhu; Cori Bradley; Lyra Griffiths; Lei Yang; Praveen Kumar Suryadevara; Jiakun Zhang; Burgess B. Freeman; R. Kiplin Guy; Michael A. Dyer (Pharmaceutical Research, 2014)

The Madagascar Fauna and Flora Group as an example of how a consortium is enabling diverse zoological and botanical gardens to contribute to biodiversity conservation in Madagascar - K. L. M. Freeman; A. Bollen; F. J. F. Solofoniaina; H. Andriamiarinoro; I. Porton; C. R. Birkinshaw (Plant Biosystems, 2014)

Characterization of Fusarium mangiferae isolates from mango malformation disease in Southern Spain - M. Crespo; E. Arrebola; F. M. Cazorla; M. Maymon; S. Freeman; J. A. Torés; A. de Vicente (European Journal of Plant Pathology, 2014)

Garden Size, Householder Knowledge, and Socio-Economic Status Influence Plant and Bird Diversity at the Scale of Individual Gardens - Yolanda van Heezik; Claire Freeman; Stefan Porter; Katharine J. M. Dickinson (Ecosystems, 2013)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Genetic analysis of the near-infrared spectral phenome of a global Eucalyptus species - J. M. O’Reilly-Wapstra; J. S. Freeman; R. Barbour; R. E. Vaillancourt; B. M. Potts (Tree Genetics & Genomes, 2013)

The effect of nicotine on sign-tracking and goal-tracking in a Pavlovian conditioned approach paradigm in rats - Matthew I. Palmatier; Kimberley R. Marks; Scott A. Jones; Kyle S. Freeman; Kevin M. Wissman; A. Brianna Sheppard (Psychopharmacology, 2013)

Reply to Comment on: Coarse clast ridge sequences as suitable archives for past storm events? Case study on the Houtman Abrolhos, Western Australia - Anja M. Scheffers; Sander R. Scheffers; Dieter H. Kelletat; Peter Squire; Lindsay Collins; Yuexing Feng; Jian‐Xin Zhao; Renaud Joannes‐Boyau; Simon Matthias May; Gerhard Schellmann; Heather Freeman (Journal of Quaternary Science, 2013)

Pesticide use and fatal injury among farmers in the Agricultural Health Study - Jenna K. Waggoner; Paul K. Henneberger; Greg J. Kullman; David M. Umbach; Freya Kamel; Laura E. Beane Freeman; Michael C. R. Alavanja; Dale P. Sandler; Jane A. Hoppin (International Archives of Occupational and Environmental Health, 2013)

Associative blocking to reward-predicting cues is attenuated in ketamine users but can be modulated by images associated with drug use - Tom P. Freeman; Celia J. A. Morgan; Fiona Pepper; Oliver D. Howes; James M. Stone; H. Valerie Curran (Psychopharmacology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Reconciling the optimal and empirical approaches to modelling stomatal conductance - Belinda E. Medlyn; Remko A. Duursma; Derek Eamus; David S. Ellsworth; I. Colin Prentice; Craig V. M. Barton; Kristine Y. Crous; Paolo de Angelis; Michael Freeman; Lisa Wingate (Global Change Biology, 2012)

Acidity controls on dissolved organic carbon mobility in organic soils - Chris D. Evans; Tim G. Jones; Annette Burden; Nick Ostle; Piotr Zieliński; Mark D. A. Cooper; Mike Peacock; Joanna M. Clark; Filip Oulehle; David Cooper; Chris Freeman (Global Change Biology, 2012)
Dissolved organic carbon ( DOC ) concentrations in surface waters have increased across much of E urope and N orth A merica, with implications for the terrestrial carbon balance, aquatic ecosystem functioning, water treatment costs and human health. Over the past decade, many hypotheses have been put forward to explain this phenomenon, from changing climate and land management to eutrophication and acid deposition. Resolution of this debate has been hindered by a reliance on correlative analyses of time series data, and a lack of robust experimental testing of proposed mechanisms. In a 4 year, four‐site replicated field experiment involving both acidifying and deacidifying treatments, we tested the hypothesis that DOC leaching was previously suppressed by high levels of soil acidity in peat and organo‐mineral soils, and therefore that observed DOC increases a consequence of decreasing soil acidity. We observed a consistent, positive relationship between DOC and acidity change at all sites. Responses were described by similar hyperbolic relationships between standardized changes in DOC and hydrogen ion concentrations at all sites, suggesting potentially general applicability. These relationships explained a substantial proportion of observed changes in peak DOC concentrations in nearby monitoring streams, and application to a UK ‐wide upland soil p H dataset suggests that recovery from acidification alone could have led to soil solution DOC increases in the range 46–126% by habitat type since 1978. Our findings raise the possibility that changing soil acidity may have wider impacts on ecosystem carbon balances. Decreasing sulphur deposition may be accelerating terrestrial carbon loss, and returning surface waters to a natural, high‐ DOC condition.

Identification of Cys94 as the distal ligand to the Fe(III) heme in the transcriptional regulator RcoM-2 from Burkholderia xenovorans - Aaron T. Smith; Katherine A. Marvin; Katherine M. Freeman; Robert L. Kerby; Gary P. Roberts; Judith N. Burstyn (JBIC Journal of Biological Inorganic Chemistry, 2012)

Cigarette smoking, alcohol intake, and thyroid cancer risk: a pooled analysis of five prospective studies in the United States - Cari M. Kitahara; Martha S. Linet; Laura E. Beane Freeman; David P. Check; Timothy R. Church; Yikyung Park; Mark P. Purdue; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

Coarse clast ridge sequences as suitable archives for past storm events? Case study on the Houtman Abrolhos, Western Australia - Anja M. Scheffers; Sander R. Scheffers; Dieter H. Kelletat; Peter Squire; Lindsay Collins; Yuexing Feng; Jian‐Xin Zhao; Renaud Joannes‐Boyau; Simon Matthias May; Gerhard Schellmann; Heather Freeman (Journal of Quaternary Science, 2012)
Prehistoric storm records are relatively scarce in most parts of the world. This article presents storm records derived from coral rubble‐based geological archives of the Houtman Abrolhos Archipelago located off the west coast of Australia, where the southernmost coral reefs of the Indian Ocean are found. Winter storm swell from the circum‐Antarctic ‘Brave Westerlies’, as well as tropical cyclone waves, have left numerous ridge systems on dozens of islands of the archipelago, all composed of coral rubble from adjacent reefs. At three islands, seven ridge systems were dated by three different methods: U‐series (68 dates), radiocarbon (64 dates), electron spin resonance (7 dates); 139 radiometric dates span the last 5500 years of the Holocene. In contrast to the geomorphological interpretation, the age sequences show ‘inversions’, hiatuses and different ages for the same ridge, all pointing to complicated ridge formation processes. Time gaps, some exceeding 1000 years, are interpreted as phases of erosion and not as phases without storm activity. Copyright © 2012 John Wiley & Sons, Ltd.

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Prefrontal Dopaminergic and Enkephalinergic Synaptic Accommodation in HIV-associated Neurocognitive Disorders and Encephalitis - Benjamin B. Gelman; Joshua G. Lisinicchia; Tianshen Chen; Kenneth M. Johnson; Kristofer Jennings; Daniel H. Freeman; Vicki M. Soukup (Journal of Neuroimmune Pharmacology, 2012)

Dealing With Uncertainty When Assessing Fish Passage Through Culvert Road Crossings - Gregory B. Anderson; Mary C. Freeman; Byron J. Freeman; Carrie A. Straight; Megan M. Hagler; James T. Peterson (Environmental Management, 2012)

Comparative epidemiology of CTX-M-14 and CTX-M-15 producing Escherichia coli: Association with distinct demographic groups in the community in New Zealand - J. T. Freeman; D. A. Williamson; H. Heffernan; M. Smith; J. E. Bower; S. A. Roberts (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evidence for scent marking in vervet monkeys? - N. J. Freeman; G. M. Pasternak; T. L. Rubi; L. Barrett; S. P. Henzi (Primates, 2012)

An Asian ambrosia beetle Euwallacea fornicatus and its novel symbiotic fungus Fusarium sp. pose a serious threat to the Israeli avocado industry - Z. Mendel; A. Protasov; M. Sharon; A. Zveibil; S. Ben Yehuda; K. O’Donnell; R. Rabaglia; M. Wysoki; S. Freeman (Phytoparasitica, 2012)

Y chromosome haplogroups and prostate cancer in populations of European and Ashkenazi Jewish ancestry - Zhaoming Wang; Hemang Parikh; Jinping Jia; Timothy Myers; Meredith Yeager; Kevin B. Jacobs; Amy Hutchinson; Laurie Burdett; Arpita Ghosh; Michael J. Thun; Susan M. Gapstur; W. Ryan Diver; et al. (Human Genetics, 2012)

High rates of susceptibility to ceftazidime among globally prevalent CTX-M-producing Escherichia coli: potential clinical implications of the revised CLSI interpretive criteria - D. A. Williamson; S. A. Roberts; M. Smith; H. Heffernan; A. Tiong; C. Pope; J. T. Freeman (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

High synteny and colinearity among Eucalyptus genomes revealed by high-density comparative genetic mapping - Corey J. Hudson; Anand R. K. Kullan; Jules S. Freeman; Danielle A. Faria; Dario Grattapaglia; Andrzej Kilian; Alexander A. Myburg; Brad M. Potts; René E. Vaillancourt (Tree Genetics & Genomes, 2012)

Analysis of doramectin in the serum of repeatedly treated pastured cattle used to predict the probability of cattle fever ticks (Acari: Ixodidae) feeding to repletion - Ronald B. Davey; J. Mathews Pound; Jerome A. Klavons; Kimberly H. Lohmeyer; Jeanne M. Freeman; Pia U. Olafson (Experimental and Applied Acarology, 2012)

Physical activity, diabetes, and thyroid cancer risk: a pooled analysis of five prospective studies - Cari M. Kitahara; Elizabeth A. Platz; Laura E. Beane Freeman; Amanda Black; Ann W. Hsing; Martha S. Linet; Yikyung Park; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

A Numerical Study of Microscale Flow Behavior in Tight Gas and Shale Gas Reservoir Systems - C. M. Freeman; G. J. Moridis; T. A. Blasingame (Transport in Porous Media, 2011)

Quantitative trait loci for foliar terpenes in a global eucalypt species - Julianne M. O’Reilly-Wapstra; Jules S. Freeman; Noel W. Davies; René E. Vaillancourt; Hugh Fitzgerald; Brad M. Potts (Tree Genetics & Genomes, 2011)

An hTERT-immortalized human urothelial cell line that responds to anti-proliferative factor - Jayoung Kim; Mihee Ji; Joseph A. DiDonato; Raymond R. Rackley; Mei Kuang; Provash C. Sadhukhan; Joshua R. Mauney; Susan K. Keay; Michael R. Freeman; Louis S. Liou; Rosalyn M. Adam (In Vitro Cellular & Developmental Biology - Animal, 2011)

Molecular diagnosis of Myxobolus spirosulcatus associated with encephalomyelitis of cultured yellowtail, Seriola quinqueradiata Temminck & Schlegel - H Yokoyama; T Yanagida; M A Freeman; T Katagiri; A Hosokawa; M Endo; M Hirai; S Takagi (Journal of Fish Diseases, 2010)
Mass mortality of cultured yellowtail, Seriola quinqueradiata , has recently been reported from fish farms in western Japan. Previous studies revealed that diseased fish were characterized by encephalomyelitis and presporogonic stages of a myxosporean‐like parasite in the spinal cord. However, the parasite has remained unidentified because of the lack of mature stages being present. Thus, in the present study, analysis of the small subunit ribosomal DNA (18S rDNA) of the parasite as well as in situ hybridization (ISH) studies using histological sections of the infected tissue was conducted. The 18S rDNA of the myxosporean had higher sequence similarities with those of bile‐duct‐infecting myxosporeans rather than those infecting nervous tissues and was identified as Myxobolus spirosulcatus . The ISH using specific probes demonstrated that the DNA amplified was derived from the multinuclear organisms found in histological sections. A highly sensitive and specific PCR‐based assay for M. spirosulcatus was developed, which revealed a high prevalence of infection in cultured yellowtail that exhibited the clinical signs of encephalomyelitis.

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Reproductive isolation and the expansion of an invasive hybrid swarm - Michael J. Blum; David M. Walters; Noel M. Burkhead; Byron J. Freeman; Brady A. Porter (Biological Invasions, 2010)

Appraising the roles of nutrient availability, global change, and functional traits during the angiosperm rise to dominance - Kevin E. Mueller; Aaron F. Diefendorf; Katherine H. Freeman; David M. Eissenstat (Ecology Letters, 2010)
Ecology Letters (2010) 13: E1–E6 Abstract To explain the rise of angiosperms during the Cretaceous, Berendse & Scheffer ( Ecol. Lett. , 12, 2009, 865) invoke feedbacks between leaf litter, soil nutrients, and growth, overlooking other factors affecting resource acquisition by Cretaceous plants. We evaluate their hypothesis, highlight alternative explanations, and emphasize use of a broader framework for understanding the angiosperm radiation.

Endotoxin exposure and lung cancer risk: a systematic review and meta-analysis of the published literature on agriculture and cotton textile workers - Virissa Lenters; Ioannis Basinas; Laura Beane-Freeman; Paolo Boffetta; Harvey Checkoway; David Coggon; Lützen Portengen; Malcolm Sim; Inge M. Wouters; Dick Heederik; Roel Vermeulen (Cancer Causes & Control, 2010)

Circulating Cytokines as Biomarkers of Alcohol Abuse and Alcoholism - Rajeshwara N. Achur; Willard M. Freeman; Kent E. Vrana (Journal of Neuroimmune Pharmacology, 2010)

QTL influencing growth and wood properties in Eucalyptus globulus - Jules S. Freeman; Simon P. Whittock; Brad M. Potts; René E. Vaillancourt (Tree Genetics & Genomes, 2009)

Red shiner invasion and hybridization with blacktail shiner in the upper Coosa River, USA - David M. Walters; Mike J. Blum; Brenda Rashleigh; Byron J. Freeman; Brady A. Porter; Noel M. Burkhead (Biological Invasions, 2008)

Description and phylogeny of Ceratomyxa anko sp. n. and Zschokkella lophii sp. n. from the Japanese anglerfish, Lophius litulon (Jordan) - M A Freeman; H Yokoyama; K Ogawa (Journal of Fish Diseases, 2008)
Two new species of myxozoans from the Japanese anglerfish, Lophius litulon , are described using myxospore morphology and small subunit rDNA sequences. Ceratomyxa anko sp. n. is a parasite of the gall bladder and had a prevalence of 57%. Mature spores of C. anko sp. n. are arcuate to crescent shaped with valves tapering to rounded tips. A prominent sutural line runs centrally between the round adjacent polar capsules containing the polar filament coiled two to three times. Spore measurements: length 10.8 (9.7–11.9) μm, width 41.9 (36.9–47.2) μm, polar capsule diameter 4.6 (4.1–5.3) μm. Ceratomyxa anko sp. n. can be distinguished from other Ceratomyxa spp. due to its spore dimensions and shape. Zschokkella lophii sp. n. is a parasite of the urinary bladder and had a prevalence of 70%. Mature spores are ellipsoidal to semicircular with bluntly pointed ends. The sutural line is curved or sinuous and the valves have no discernable surface ornamentation. Two almost spherical polar capsules are located separately in the ends of the spore, opening in almost opposite directions and contain the polar filament with five coils. Spore measurements: length 20.1 (16.8–24.0) μm, width 14.9 (12.7–16.8) μm, polar capsule diameter 5.1 (3.6–5.8) μm. Zschokkella lophii sp. n. can be distinguished from other Zschokkella spp. due to the terminal opening of the polar capsules within the spores and the site of infection within the host fish. In the phylogenetic analyses, C. anko sp. n. grouped with other members of the same genus forming a monophyly. Zschokkella lophii sp. n. forms a discrete clade with another Zschokkella sp. that infects the urinary bladder of marine fish. This grouping forms a sister clade to one containing members of the genus Parvicapsula , all of which are parasites of the urinary system in marine fish.

Otoacoustic emissions in humans, birds, lizards, and frogs: evidence for multiple generation mechanisms - Christopher Bergevin; Dennis M. Freeman; James C. Saunders; Christopher A. Shera (Journal of Comparative Physiology A, 2008)

Molecular characterization of mesophilic and thermophilic sulfate reducing microbial communities in expanded granular sludge bed (EGSB) reactors - Stephanie A. Freeman; Reyes Sierra-Alvarez; Mahmut Altinbas; Jeremy Hollingsworth; Alfons J. M. Stams; Hauke Smidt (Biodegradation, 2008)

The role of selenium in protecting plants against prairie dog herbivory: implications for the evolution of selenium hyperaccumulation - Colin F. Quinn; John L. Freeman; Miriam L. Galeas; Erin M. Klamper; Elizabeth A. H. Pilon-Smits (Oecologia, 2008)

Agricultural management affects evolutionary processes in a migratory songbird - NOAH G. PERLUT; COREY R. FREEMAN‐GALLANT; ALLAN M. STRONG; THERESE M. DONOVAN; C. WILLIAM KILPATRICK; NATHAN J. ZALIK (Molecular Ecology, 2008)
Hay harvests have detrimental ecological effects on breeding songbirds, as harvesting results in nest failure. Importantly, whether harvesting also affects evolutionary processes is not known. We explored how hay harvest affected social and genetic mating patterns, and thus, the overall opportunity for sexual selection and evolutionary processes for a ground‐nesting songbird, the Savannah sparrow ( Passerculus sandwichensis ). On an unharvested field, 55% of females were in polygynous associations, and social polygyny was associated with greater rates of extra‐pair paternity (EPP). In this treatment, synchrony explained variation in EPP rates, as broods by more synchronous females had more EPP than broods by asynchronous females. In contrast, on a harvested field, simultaneous nest failure caused by haying dramatically decreased the overall incidence of EPP by increasing the occurrence of social monogamy and, apparently, the ability of polygynous males to maintain paternity in their own nests. Despite increased social and genetic monogamy, these haying‐mediated changes in mating systems resulted in greater than twofold increase in the opportunity for sexual selection. This effect arose, in part, from a 30% increase in the variance associated with within‐pair fertilization success, relative to the unharvested field. This effect was caused by a notable increase (+110%) in variance associated with the quality of social mates following simultaneous nest failure. Because up to 40% of regional habitat is harvested by early June, these data may demonstrate a strong population‐level effect on mating systems, sexual selection, and consequently, evolutionary processes.

Extent of the last ice sheet in northern Scotland tested with cosmogenic 10 Be exposure ages - William M. Phillips; Adrian M. Hall; Colin K. Ballantyne; Steven Binnie; Peter W. Kubik; Stewart Freeman (Journal of Quaternary Science, 2008)
The extent of the last British–Irish Ice Sheet (BIIS) in northern Scotland is disputed. A restricted ice sheet model holds that at the global Last Glacial Maximum (LGM; ca. 23–19 ka) the BIIS terminated on land in northern Scotland, leaving Buchan, Caithness and the Orkney Islands ice‐free. An alternative model implies that these three areas were ice‐covered at the LGM, with the BIIS extending offshore onto the adjacent shelves. We test the two models using cosmogenic 10 Be surface exposure dating of erratic boulders and glacially eroded bedrock from the three areas. Our results indicate that the last BIIS covered all of northern Scotland during the LGM, but that widespread deglaciation of Caithness and Orkney occurred prior to rapid warming at ca. 14.5 ka. Copyright © 2008 John Wiley & Sons, Ltd.

Methyl sulfides as intermediates in the anaerobic oxidation of methane - James J. Moran; Emily J. Beal; Jennifer M. Vrentas; Victoria J. Orphan; Katherine H. Freeman; Christopher H. House (Environmental Microbiology, 2008)
Summary While it is clear that microbial consortia containing Archaea and sulfate‐reducing bacteria (SRB) can mediate the anaerobic oxidation of methane (AOM), the interplay between these microorganisms remains unknown. The leading explanation of the AOM metabolism is ‘reverse methanogenesis’ by which a methanogenesis substrate is produced and transferred between species. Conceptually, the reversal of methanogenesis requires low H 2 concentrations for energetic favourability. We used 13 C‐labelled CH 4 as a tracer to test the effects of elevated H 2 pressures on incubations of active AOM sediments from both the Eel River basin and Hydrate Ridge. In the presence of H 2 , we observed a minimal reduction in the rate of CH 4 oxidation, and conclude H 2 does not play an interspecies role in AOM. Based on these results, as well as previous work, we propose a new model for substrate transfer in AOM. In this model, methyl sulfides produced by the Archaea from both CH 4 oxidation and CO 2 reduction are transferred to the SRB. Metabolically, CH 4 oxidation provides electrons for the energy‐yielding reduction of CO 2 to a methyl group (‘methylogenesis’). Methylogenesis is a dominantly reductive pathway utilizing most methanogenesis enzymes in their forward direction. Incubations of seep sediments demonstrate, as would be expected from this model, that methanethiol inhibits AOM and that CO can be substituted for CH 4 as the electron donor for methylogenesis.

Microglial Activation is Required for Aβ Clearance After Intracranial Injection of Lipopolysaccharide in APP Transgenic Mice - Donna L. Herber; Mary Mercer; Lisa M. Roth; Keisha Symmonds; Jessica Maloney; Nedda Wilson; Melissa J. Freeman; Dave Morgan; Marcia N. Gordon (Journal of Neuroimmune Pharmacology, 2007)

A decade of the Super Dual Auroral Radar Network (SuperDARN): scientific achievements, new techniques and future directions - G. Chisham; M. Lester; S. E. Milan; M. P. Freeman; W. A. Bristow; A. Grocott; K. A. McWilliams; J. M. Ruohoniemi; T. K. Yeoman; P. L. Dyson; R. A. Greenwald; T. Kikuchi; et al. (Surveys in Geophysics, 2007)

Elucidation of pectinolytic enzyme activities of a non-pathogenic watermelon pathogen mutant, Fusarium oxysporum f.sp. niveum M87 - P. Basaran; M. Ozcan; Y. Denisov; S. Freeman (Australasian Plant Pathology, 2007)

Hyperhydration prior to a simulated second day of the 3-day moderate intensity equestrian competition does not cause arterial hypoxemia in Thoroughbred horses - B. S. Tennent-Brown; T. E. Goetz; M. Manohar; A. S. Hassan; D. E. Freeman; J. S. Bundy; M. R. Evans (European Journal of Applied Physiology, 2006)

How to build a myofibril - Joseph W. Sanger; Songman Kang; Cornelia C. Siebrands; Nancy Freeman; Aiping Du; Jushuo Wang; Andrea L. Stout; Jean M. Sanger (Journal of Muscle Research and Cell Motility, 2006)

Does modafinil activate the locus coeruleus in man? Comparison of modafinil and clonidine on arousal and autonomic functions in human volunteers - R. H. Hou; C. Freeman; R. W. Langley; E. Szabadi; C. M. Bradshaw (Psychopharmacology, 2005)

An extinction cue reduces spontaneous recovery of ataxic ethanol tolerance in rats - Douglas C. Brooks; Joanne M. Vaughn; Andrew J. Freeman; Amanda M. Woods (Psychopharmacology, 2004)

Admixture and diversity in West African cattle populations - A. R. FREEMAN; C. M. MEGHEN; D. E. MacHUGH; R. T. LOFTUS; M. D. ACHUKWI; A. BADO; B. SAUVEROCHE; D. G. BRADLEY (Molecular Ecology, 2004)
We present a population genetic analysis of microsatellite variation in 16 West African cattle populations. West Africa represents a unique juxtaposition of different climatic and ecological zones in a relatively small geographical area. While more humid coastal regions are inhabited by the tsetse fly, a vector which spreads trypanosomiasis among cattle, the disease is not transmitted in the drier areas outside this zone. This is the most thorough study of genetic diversity in cattle within this area, which contains genetically important trypanotolerant Bos taurus breeds. Genetic relationships among the many breeds are examined and levels of diversity are assessed. Admixture levels were determined using a variety of methods. Ancestry informative or population‐associated alleles (PAAs) were selected using populations from India, the Near East and Europe. Multivariate analysis, the admix program and model‐based Bayesian admixture analysis approaches were also employed. These analyses reveal the direct impact of ecological factors and the profound effect of admixture on the cattle of this region. They also highlight the importance of efforts to prevent further dilution of African taurine breeds by B. indicus cattle.

Identification ofTrichoderma biocontrol isolates to clades according to ap-PCR and ITS sequence analyses - M. Maymon; D. Minz; O. Barbul; A. Zveibil; Y. Elad; S. Freeman (Phytoparasitica, 2004)

Using molecular markers with high mutation rates to obtain estimates of relative population size and to distinguish the effects of gene flow and mutation: a demonstration using data from endemic Mauritian skinks - R. A. Nichols; K. L. M. Freeman (Molecular Ecology, 2004)
We propose a method of analysing genetic data to obtain separate estimates of the size ( N p ) and migration rate ( m p ) for the sampled populations, without precise prior knowledge of mutation rates at each locus (µ L ). The effects of migration and mutation can be distinguished because high migration has the effect of reducing genetic differentiation across all loci, whereas a high mutation rate will only affect the locus in question. The method also takes account of any differences between the spectra of immigrant alleles and of new mutant alleles. If the genetic data come from a range of population sizes, and the loci have a range of mutation rates, it is possible to estimate the relative sizes of the different N p values, and likewise the m p and the µ L . Microsatellite loci may also be particularly appropriate because loci with a high mutation rate can reach mutation–drift–migration equilibrium more quickly, and because the spectra of mutants arriving in a population can be particularly distinct from the immigrants. We demonstrate this principle using a microsatellite data set from Mauritian skinks. The method identifies low gene flow between a putative new species and populations of its sister species, whereas the differentiation of two other populations is attributed to small population size. These distinct interpretations were not readily apparent from conventional measures of genetic differentiation and gene diversity. When the method is evaluated using simulated data sets, it correctly distinguishes low gene flow from small population size. Loci that are not at mutation–migration–drift equilibrium can distort the parameter estimates slightly. We discuss strategies for detecting and overcoming this effect.

Analysis of soil wetting and solute transport in subsurface trickle irrigation - Claire M. Cote; Keith L. Bristow; Philip B. Charlesworth; Freeman J. Cook; Peter J. Thorburn (Irrigation Science, 2003)

A hyperparasitic microsporidian infecting the salmon louse, Lepeophtheirus salmonis : an rDNA‐based molecular phylogenetic study - M A Freeman; A S Bell; C Sommerville (Journal of Fish Diseases, 2003)
The sea louse, Lepeophtheirus salmonis , is an obligate ectoparasitic copepod that lives on the external surface of salmonid fish. It is the most common ectoparasite of marine cage‐reared salmonids, causing major economic loss to the aquaculture industry. During a sea louse monitoring programme, samples of L. salmonis were found to harbour an unreported microsporidian parasite. The microsporidian was observed in pre‐adult and adult stages of both male and female copepods, with a prevalence of up to 5%. Unfixed spores were slightly pyriform in shape measuring 2.34 μ m by 1.83 μ m (±0.01 μ m) and were not observed to be enclosed by a sporophorous vesicle. The microsporidian infection was observed in all areas of the copepods’ body, xenoma‐like cysts forming directly under the cuticle in the epidermal tissue layer. In the present study, rDNA (530f–580r) sequence data gathered from the unidentified microsporidian parasite isolated from infected sea lice were compared with equivalents available in the databases in an attempt to identify its systematic position. The microsporidian was found to group within the phylogenetic clade containing the family Enterocytozoonidae, being most similar to members of the intranuclear genus Nucleospora . This is the first report of a hyperparasitic microsporidian infecting a caligid copepod.

Differences in native soil ecology associated with invasion of the exotic annual chenopod, Halogeton glomeratus - Jeffrey J. Duda; D. Carl Freeman; John M. Emlen; Jayne Belnap; Stanley G. Kitchen; John C. Zak; Edward Sobek; Mary Tracy; James Montante (Biology and Fertility of Soils, 2003)

Fertilizer use in semi-arid areas of Kenya: analysis of smallholder farmers' adoption behavior under liberalized markets - H. Ade Freeman; John M. Omiti (Nutrient Cycling in Agroecosystems, 2003)

Early and late patterns of stimulus-related activity in auditory cortex of trained animals - F. W. Ohl; M. Deliano; H. Scheich; W. J. Freeman (Biological Cybernetics, 2003)

Potential role of the EPEC translocated intimin receptor (Tir) in host apoptotic events - H. R. Malish; N. L. Freeman; D. V. Zurawski; P. Chowrashi; J. C. Ayoob; J. W. Sanger; J. M. Sanger (Apoptosis, 2003)

A thin-film electrochemical study of the "blue" copper proteins, auracyanin A and auracyanin B, from the photosynthetic bacterium Chloroflexus aurantiacus: the reduction potential as a function of pH - Melissa B. Rooney; Michael J. Honeychurch; Fabiola M. Selvaraj; Robert E. Blankenship; Alan M. Bond; Hans C. Freeman (JBIC Journal of Biological Inorganic Chemistry, 2003)

CYP3A4-V and prostate cancer in African Americans: causal or confounding association because of population stratification? - Rick A. Kittles; Weidong Chen; Ramesh K. Panguluri; Chiledum Ahaghotu; Aaron Jackson; Clement A. Adebamowo; Robin Griffin; Tyisha Williams; Flora Ukoli; Lucile Adams-Campbell; John Kwagyan; William Isaacs; et al. (Human Genetics, 2002)

Variation at the major histocompatibility complex in Savannah sparrows - Corey R. Freeman‐Gallant; Elizabeth M. Johnson; Fiorella Saponara; Matthew Stanger (Molecular Ecology, 2002)
The class I and class II genes of the major histocompatibility complex ( Mhc ) encode dimeric glycoproteins responsible for eliciting the adaptive immune response of vertebrates. Recent work with birds suggests that the number, size, and arrangement of these genes can differ markedly across species, although the extent of this variation, and its causes and consequences, are poorly understood. We have used a 157‐base‐pair (bp) portion of the second exon of a class II B gene to probe the Mhc in a free‐living population of Savannah sparrows ( Passerculus sandwichensis ). Segregation analysis of Mhc bands suggests that class II B genes can be found in two independently assorting clusters, as previously described for domestic chickens ( Gallus gallus ) and ring‐necked pheasants ( Phasianus colchicus ) but unlike gene organization in mammals. The Mhc in Savannah sparrows appears large (with many class II B genes) and variable; we found 42 unique genotypes among 48 adults breeding on Kent Island, New Brunswick, Canada in 1995. Savannah sparrows are long‐distance migrants, and these results support recent predictions that migratory birds should show higher levels of Mhc polymorphism and/or a greater number of genes than sedentary species. Savannah sparrows are also socially polygynous with high levels of extra‐pair paternity, suggesting that a history of sexual selection might also influence the size and/or structure of the avian Mhc .

Radiation hybrid mapping of 70 rat genes from a data set of differentially expressed genes - Caroline A. Wallace; Saira Ali; Anne M. Glazier; Penny J. Norsworthy; Danilo C. Carlos; James Scott; Tom C. Freeman; Lawrence W. Stanton; Anne E. Kwitek; Timothy J. Aitman (Mammalian Genome, 2002)

4. Histamine in growth, development and cancer¶Further evidence that histamine H1-antagonists cause joint weakness in rat foetuses - G. Sturman; P. Freeman; H. M. Meade; N. A. Seeley (Inflammation Research, 2002)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

A novel method for implantation of LNCaP prostate tumor cells under the renal capsule - Rosalyn M. Adam; Anna Orsola; Michael R. Freeman (In Vitro Cellular & Developmental Biology - Animal, 2001)

Administration of FGF-1 through transfected cells alleviates MPTP toxicity in mice - Robert N. Mclay; Scott M. Freeman; James E. Zadina (Neurotoxicity Research, 2001)

A NOVEL METHOD FOR IMPLANTATION OF LNCaP PROSTATE TUMOR CELLS UNDER THE RENAL CAPSULE - ROSALYN M. ADAM; ANNA ORSOLA; MICHAEL R. FREEMAN (In Vitro Cellular & Developmental Biology - Animal, 2001)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

Seasonal soil‐surface carbon fluxes from the root systems of young Pinus radiata trees growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; Freeman J. Cook; David Whitehead; John A. Adams (Global Change Biology, 2000)
Summary Elevated atmospheric CO 2 concentration may result in increased below‐ground carbon allocation by trees, thereby altering soil carbon cycling. Seasonal estimates of soil surface carbon flux were made to determine whether carbon losses from Pinus radiata trees growing at elevated CO 2 concentration were higher than those at ambient CO 2 concentration, and whether this was related to increased fine root growth. Monthly soil surface carbon flux density ( f ) measurements were made on plots with trees growing at ambient (350) and elevated (650 μmol mol −1 ) CO 2 concentration in large open‐top chambers. Prior to planting the soil carbon concentration (0.1%) and f (0.28 μmol m −2 s −1 at 15 °C) were low. A function describing the radial pattern of f with distance from tree stems was used to estimate the annual carbon flux from tree plots. Seasonal estimates of fine root production were made from minirhizotrons and the radial distribution of roots compared with radial measurements of f . A one‐dimensional gas diffusion model was used to estimate f from soil CO 2 concentrations at four depths. For the second year of growth, the annual carbon flux from the plots was 1671 g y −1 and 1895 g y −1 at ambient and elevated CO 2 concentrations, respectively, although this was not a significant difference. Higher f at elevated CO 2 concentration was largely explained by increased fine root biomass. Fine root biomass and stem production were both positively related to f. Both root length density and f declined exponentially with distance from the stem, and had similar length scales. Diurnal changes in f were largely explained by changes in soil temperature at a depth of 0.05 m. Ignoring the change of f with increasing distance from tree stems when scaling to a unit ground area basis from measurements with individual trees could result in under‐ or overestimates of soil‐surface carbon fluxes, especially in young stands when fine roots are unevenly distributed.

Sequence and comparative structural analysis of the murine leukaemia virus amphotropic strain 4070A RNase H domain - P. L. Ey; N. L. Freeman; B. Bela; P. M. Haese; P. Li; J. L. McInnes (Archives of Virology, 1999)

Cell-specific activation of the HB-EGF and ErbB1 genes by stretch in primary human bladder cells - Hiep T. Nguyen; John M. Park; Craig A. Peters; Rosalyn M. Adam; Anna Orsola; Anthony Atala; Michael R. Freeman (In Vitro Cellular & Developmental Biology - Animal, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Peroxidase-Catalyzed Oxidation of 2,4,6-Trichlorophenol - F. W. Wiese; H. C. Chang; R. V. Lloyd; J. P. Freeman; V. M. Samokyszyn (Archives of Environmental Contamination and Toxicology, 1998)

Developmental instability in gynodioecious Teucrium lusitanicum - CONCEPCION L. Alados; TERESA Navarro; BALTASAR Cabezudo; JOHN M. Emlen; CARL Freeman (Evolutionary Ecology, 1998)

Effects of histamine H 2 -antagonists on pre- and post-natal development in the rat - P. Freeman; G. Sturman; A.-M. Suhonen; H. M. Meade; N. A. Seeley (Inflammation Research, 1997)

Factors affecting the extent of fetal fragility induced by histamine H 1 antagonists - G. Sturman; P. Freeman; H. M. Meade; N. A. Seeley (Inflammation Research, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Cohesive sediment transport on an inter-tidal zone under combined wave-tidal flow - D. P. Freeman; L. E. Coates; M. C. Ockenden; W. Roberts; J. R. West (Aquatic Ecology, 1994)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Mitochondrial malic enzyme in mosaic skeletal muscle of mouse chimeras - P. M. Frair; P. M. Strasberg; K. B. Freeman; A. C. Peterson (Biochemical Genetics, 1979)

Neural dynamics under noise in the olfactory system - S. M. Ahn; Walter J. Freeman (Biological Cybernetics, 1975)

“Errata” in vol. IV, No. 4, April, 1927 - B. E. Brown; Freeman Weiss; Philip Brierley; R. C. Wright; W. M. Peacock (American Journal of Potato Research, 1927)

Effect of fertilizer on potato tubers - B. E. Brown; Freeman Weiss; Philip Brierley; R. C. Wright; W. M. Peacock (American Journal of Potato Research, 1927)